First report of Fusarium weifangense, F. puerense and F. asiaticum causing leaf spot disease on Morus alba L. in China - Mei Lei; Rong Xiao; Lixia Zhang; Yu Tian; Zhongrong Zheng; Zehui Zhao; Tingting Zhao; Zhu Li; Haixia Ding (Crop Protection, 2026)

Assessments of gully erosion susceptibility in typical thick-layer Mollisol region of Northeast China - Binglong Wu; Fenli Zheng; Ximeng Xu; Yucheng Fu; Dennis C. Flanagan; Rong Li; Jiaqiong Zhang; Bin Wang; Jinxia Fu (Soil and Tillage Research, 2026)

Reconstruction of the Cretaceous palaeo-plateau in South China: Insights from geochemical thermobarometry and isostasy modelling - Hanqiao Zheng; Junfeng Gong; Rong Yang; Ruohong Jiao; Junqing He; Fengqi Zhang; Hongdan Deng; Jiakang Huang; Zhiquan Yu; Yunlong Wang; Hanlin Chen; Shufeng Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Vessel-derived metal ions catalyze the accumulation of representative aging markers in multi-round Jiang-flavor base liquor - Wei Zhang; Shi-Yi Wang; Man-Si Niu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Rong-Kun Tu; Song-Tao Wang; Cai-Hong Shen; Jun-Jie Jia; Xiao-Juan Zhang; Zheng-Hong Xu (Food Research International, 2026)

Multi-omics integration elucidates molecular mechanisms underlying distinctive meat quality in Liping cattle versus Angus hybrid and Simmental breeds - Longxin Xu; Xin Wang; Yuanfeng Zhao; Chunxia Zheng; Jing Liu; Kaikai Zhang; Wenzhang Zhou; Rong Yang; Di Zhou; Zhongling Jian; Yongcai Zhu; Junda Wu; et al. (Food Research International, 2026)

Multi-omics analysis reveals coordinated epigenetic dysregulation in atrazine-induced dopaminergic neurotoxicity - Shuohan Ning; Zheng Liu; Yanshu Li; Rong Zhang (Food and Chemical Toxicology, 2026)

Synergistic room-temperature NH3 sensing: TiO2/g-C3N4 heterojunction with UV-enhanced performance for food freshness monitoring - Haineng Bai; Chenjie Wang; Yang Yu; Yiru Chen; Cheng Feng; Yunxiao Du; Yamin Feng; Weifeng Liu; Kuili Liu; Sihua Zhou; Fuqiang Guo; Qingfeng Li; et al. (Chemical Engineering Journal, 2026)

Spatiotemporal temperature trajectories underpin predictive modeling of microbial succession in single-batch high-temperature daqu solid-state fermentation - Jun-Jie Fu; Wei Shi; Han-Jun Shen; Sheng-Bing Yang; Bo Ren; Rong-Ze Ren; Xiao-Juan Zhang; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Song-Tao Wang; Su-Yi Zhang; et al. (Bioresource Technology, 2026)

Impact of heat-moisture treatment on cooking characteristics, structural features, and low digestion of japonica rice - Rong Zhou; Jingyi Zheng; Zhengyu Jin; Tao Zhang; Ming Miao (Food Bioscience, 2026)

Electromechanically reconfigurable graphene-hydrogel sensor with stress-buffering interface for multi-functional sensing - Yi Wang; Chenling Wu; Yixiao Li; Kun Zheng; Tong Li; Yutao Song; Chan Ye; Zheng Fang; Chenxin Zhu; Ming Zhang; Rong Yang; Lei Liao (Chemical Engineering Journal, 2026)

Molecular mechanism of anammox granular sludge disintegration caused by polyethylene terephthalate micro/nanoplastics: a new perspective based on quorum sensing - Chaofan Xie; Dongyue Li; Jun Li; Jiarui Li; Muchen Yin; Yanshuo Wu; Chi Zhang; Rong Luo; Yuxi Zhu; Zehao Zhang; Zhaoming Zheng; Yongzhen Peng (Bioresource Technology, 2026)

Temporal trends in toxicities and major drivers of polycyclic aromatic hydrocarbon emissions in China from 1960 to 2019 - Xiao Yun; Huizhong Shen; Jin Li; Yuanzheng Zhang; Shuxiu Zheng; Rong Dai; Jinghang Wang; Haoran Xu; Wenxiao Zhang; Guofeng Shen; Jianmin Ma; Shu Tao (Atmospheric Environment, 2026)

Mechanistic insights and mitigation strategies for brominated dioxin formation from thermal treatment of hexabromocyclododecane waste - Heng Zhang; Lyumeng Ye; Junkai Lin; Zhiyuan Xu; Rong Jin; Dongyao Chen; Xin Zhou; Bingcheng Lin; Minghui Zheng (Waste Management, 2026)

Long-term mechanical response of shield tunnel linings in consolidating soft ground - You-Bin Yang; Jun-Jie Zheng; Rong-Jun Zhang; Hai-Bo Wang; Feng-Juan Tao (Transportation Geotechnics, 2026)

Algicidal characteristics and mechanism of a newly identified bacterium Pseudomonas fulva EH5 against Microcystis aeruginosa - Rong Xiang; Tongpeng Jia; Geqi Zhang; Xue Sun; Nianjun Xu; Binghui Zheng (Journal of Hazardous Materials, 2026)

Assessing cognitive impairment in epilepsy using Arterial spin-labeled (ASL) perfusion imaging - Qiuyan Chen; Jie Zhang; Rong Chen; Yameng Qin; Xu Wang; Qiang Liu; Zheng Yin; Ping Yang; Feng Rao; Longnan Wang; Mengyun Li; Yanzi Jin; et al. (Brain Imaging and Behavior, 2026)

The Study on the Biological Characteristics of Photobacterium damselae subsp. damselae Affected by the Deletion of the Iron Uptake System Genes tonB1 and tonB2 - Hua Jiang; Yufei Ji; Zhiqi Zhang; Yongxiang Yu; Chunyuan Wang; Yingeng Wang; Xiaojun Rong; Aijun Ma; Shuyi Li; Zheng Zhang (Fishes, 2026)
Photobacterium damselae subsp. damselae (PDD), a marine fish pathogen, has an unclear contribution of tonB genes to iron acquisition and pathogenicity. ΔtonB1-PDD and ΔtonB2-PDD mutants as well as their complemented strains were generated via homologous recombination from the virulent strain PDD1605. Growth was evaluated by monitoring OD600 with viable-count calibration, intracellular iron was measured using a colorimetric assay, biofilm was detected by crystal violet staining, transcription was analyzed through qRT-PCR, and pathogenicity was assessed via an 8-day intramuscular challenge in black rockfish (Sebastes schlegelii). Under iron limitation induced by 100 μM 2,2′-dipyridyl, the maximum density decreased from 4.51 × 108 CFU/mL in wild-type (WT-PDD) to 4.00 × 108 and 3.64 × 108 CFU/mL in ΔtonB1-PDD and ΔtonB2-PDD respectively, and was largely restored after complementation. The intracellular iron content declined from 3.75 × 10−4 ± 4.00 × 10−6 nmol/106 cells in WT-PDD to 3.13 × 10−4 ± 1.05 × 10−5 nmol/106 cells in ΔtonB1-PDD and 2.55 × 10−4 ± 2.00 × 10−5 nmol/106 cells in ΔtonB2-PDD. Compared with WT-PDD, biofilm formation was reduced by 22.1% in ΔtonB1-PDD and by 24.8% in ΔtonB2-PDD. Deletion of tonB2 induced mild yet statistically significant transcriptional alterations in multiple iron acquisition and virulence-related genes, while colony morphology, swarming motility, hemolysis, phospholipase activity, biochemical traits, and antimicrobial susceptibility remained unchanged. In the high-dose challenge assay, WT-PDD caused 100% mortality within 2 days, whereas ΔtonB1-PDD and ΔtonB2-PDD caused 17/20 and 18/20 deaths respectively; all infected groups reached 100% mortality by day 3. In the low-dose challenge assay, WT-PDD, ΔtonB1-PDD, and ΔtonB2-PDD caused 12/20, 12/20, and 13/20 deaths by day 2, with cumulative mortalities reaching 80%, 70%, and 80% by day 8, respectively. Kaplan–Meier analysis detected no significant differences among the survival curves at either challenge dose. These findings suggest that tonB1 and tonB2 play roles in iron acquisition, low-iron adaptation, and biofilm formation, with tonB2 deletion exerting greater effects on growth and intracellular iron accumulation under iron-limited conditions.

Retraction notice to “Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study” [Sci. Total Environ. 883 (2023) 163662] - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

N(7)-methylguanosine modification of mitochondrial tRNA-Trp drives myocardial injury induced by silicon carbide nanoparticles - Qingping Liu; Tao Zhang; Mengruo Wang; Peilin Zheng; Wen Gu; Yujia Xie; Yaxian Pang; Lei Bao; Haijing Zhang; Yujie Niu; Yufei Dai; Rong Zhang (Journal of Hazardous Materials, 2026)

Reducing environmental footprints of food consumption in urban and rural China: A scenario-based optimization towards sustainable diets - Zheng Guo; Junjie Zhao; Sophia Shuang Chen; Jialong Xu; Yi Zhang; Rong Li; Yingyi Ma; Enkang Li; Giri Raj Kattel (Journal of Environmental Management, 2026)

Acquisitive, diverse tree stands resist vine invasion via contrasting temporal effects on crown volume and herb cover - Li Zhang; Liting Zheng; Marc W. Cadotte; Charles A. Nock; Baiyu Yang; Zhiming Hu; Ciliang Zhao; Wen-Hui You; En-Rong Yan (Forest Ecology and Management, 2026)

Mechanistic insights into triclocarban-induced skin barrier disruption via integrating imaging localization, multi-omics, and network toxicology - Jingwen Zheng; Run Guo; Rong Zhang; Xinyu Liu; Rouyue Guo; Haozheng Li; Juntong Wei; Yuxin Zheng; Hongna Zhang (Environmental Pollution, 2026)

SRP-LNP@IL-10 nanotherapy combined with neural stem cells couples inflammation suppression with neural regeneration after spinal cord injury via the STAT3-SOCS3-BDNF axis - Ying Zhang; Honghai You; Yongxiang Zhang; Haoteng Chen; Yifeng Zheng; Weiwei Sun; Rong Xie; Tong Zhao (Chemical Engineering Journal, 2026)

pH-responsive, self-lubricating hyaluronic acid-chondroitin sulfate-chitosan hydrogel for articular cartilage repair - Haofeng Qiu; Jingfang Zheng; Zheyu Yao; Ximing Cai; Gaoke Pan; Xufeng Mao; Xin Zhao; Lei Shao; Dangsheng Xiong; Rong Wang; Yi Zhang (Carbohydrate Polymers, 2026)

Synergistic effects of pyrite and thiols on hydroxyl radical production during oxygenation - Rong Chen; Dan Zheng; Yuting Luo; Menghu Wang; Peng Zhang; Na Yang (Chemical Geology, 2026)

An Indicator System for Evaluating the Powerhouse of Meteorological Science and Technology: Design and Preliminary Application - Chaolin Zhang; Xudong Liang; Min Wen; Jianjun He; Wenjuan Zhang; Chang Liu; Qing Sun; Rong Yu; Xiaolu Yan; Zhu Zhang; Qihua Jin; Aili Shi; et al. (Journal of Meteorological Research, 2026)

Additive effects of heat and volatile organic compounds co-exposure on metabolic syndrome: evidence from petrochemical workers in China - Minhua Li; Rui Xu; Yilin Zhang; Shanshan Du; Rong Xu; Qing Zu; Zihu Lv; Wei Zheng; Weimin Ye; Jianjun Xiang (International Archives of Occupational and Environmental Health, 2026)

Sedimentary DNA and Fossil Archives Reveal Long‐Term Phytoplankton Shifts and Their Biogeochemical Influence in a Subtropical Lake - Yu Zhao; Jianan Zheng; Meifang Zhong; Wenxiu Zheng; Bo Qin; Kexin Zhu; Chenxue Zhang; Yanjie Zhao; Enlou Zhang; Eric Capo; Rong Wang (Molecular Ecology, 2026)
Understanding long‐term phytoplankton community dynamics is essential for assessing ecological resilience and informing lake management under global change. However, centennial‐scale patterns of phytoplankton dynamics remain poorly resolved due to the limited taxonomic resolution of traditional fossil‐based paleoecological approaches. In this study, a combination of sedimentary DNA (sedDNA) and subfossil diatom analysis was used to investigate changes in the phytoplankton community over the past two centuries and associated sedimentary biogeochemical responses in Lake Xiliang, a subtropical lake in the Yangtze River Basin, China. The sedDNA data captured major shifts in both eukaryotic and cyanobacterial communities, revealing distinct ecological phases linked to human activities and regional climate warming. Under near‐natural conditions with minimal human disturbance, phytoplankton communities typically exhibit low diversity and are characterized by oligotrophic taxa such as xanthophytes and Gyrosigma . After the 1930s, increases in epiphytic Staurosira and declines in tychoplanktonic Aulacoseira suggest reduced river–lake connectivity and weaker water‐column turbulence following the construction of the Jinshui Sluice, likely facilitating macrophyte expansion. In recent decades, intensified anthropogenic pressures combined with regional warming have driven a shift toward more diverse phytoplankton assemblages enriched in cyanobacteria, reflecting elevated nutrient inputs and rising temperatures. The observed associations between phytoplankton community changes and sedimentary geochemical proxies suggest that phytoplankton dynamics may not only have responded to environmental change but also contributed to sedimentary biogeochemical cycling, particularly total organic carbon accumulation and calcium‐related processes such as photosynthesis‐induced carbonate precipitation. These findings illustrate long‐term phytoplankton community dynamics and underscore the value of sedDNA for reconstructing ecological trajectories in lake ecosystems.

Docking Collision Response of an Underwater Mooring Suspension Docking System - Hua Tan; Zhen Lv; Rong Zheng; Guangzhi Zhang (Journal of Marine Science and Engineering, 2026)
Suspension docking systems offer significant application potential in autonomous underwater docking operations because of their deployment and recovery convenience. This study investigated the interaction between an axisymmetric, underactuated autonomous underwater vehicle (AUV) and a suspended guiding hood docking device (DOCK). The effects of collision velocity, collision location, collision angle, mass, and moment of inertia on the post-collision kinematic states of both bodies are analyzed. Previous studies have typically determined AUV parameters using empirical formulas, whereas few have clearly described the calibration procedure for the hydrodynamic drag coefficients of a suspended guiding hood DOCK. In this study, the hydrodynamic coefficients of both the AUV and the DOCK were determined using STAR-CCM+ and embedded into the ADAMS built-in functions to construct a physically more realistic simulation model. Subsequently, water tank experiments were conducted for suspension docking collisions. The validity of the simulation model was verified by comparing the kinematic states of the DOCK and AUV observed from the simulations and experiments. Based on the established model, the docking dynamics under various operating conditions were simulated. The simulation results indicate that the AUV mass should not exceed twice the mass of the DOCK, and the moment of inertia of the DOCK should be maximized. The risk of suspension docking failure increases significantly when the mooring line length exceeds 40 m, and the negative buoyancy of the DOCK should be at least 300 N. These findings provide critical guidance for improving the success rate of suspension docking operations.

Quantifying the light interception and canopy photosynthesis of strip intercropping system based on 3D canopy photosynthesis model - Si-Rong Huang; Qing-Feng Song; Zheng Guo; Qiu-Feng Long; Li-Sha Zhang; Yue Li; Yuan Yang; Xiao-Chun Wang; Feng Yang; Tai-Wen Yong; Jiang Liu; Yan-Hong Yan; et al. (Computers and Electronics in Agriculture, 2026)

First case report: Severe mass mortality in intensively cultured black scraper (Thamnaconus modestus) caused by nervous necrosis virus infection - Zhiqi Zhang; Yongxiang Yu; Chunyuan Wang; Zhen Meng; Yingeng Wang; Xiaojun Rong; Meijie Liao; Bin Li; Wenlong Li; Xinzhang Ji; Xiaoyan Cheng; Zheng Zhang (Aquaculture, 2026)

Multidimensional effects of personalized exercise intervention in type 2 diabetes: a randomized controlled trial - Dan Liu; Di Cheng; Qinyi Wang; Ying Zhang; Piao Kang; Chufan Zhao; Hongfeng Mao; Jing Qu; Sheng Liu; Xiaojing Gao; Rui Han; Jingyi Guo; et al. (Science Bulletin, 2026)

Sodium alginate bead flotation assisted by cationic cellulose nanofibers for polystyrene microplastic removal - Linjuan Zhang; Hao Wen; Kemin Wei; Xichen Zheng; Jia He; Manli Wang; Peng Wei; Shaoli Fan; Guiwen Rong (Process Safety and Environmental Protection, 2026)

Current warming exceeds medieval warm period in impact on Tibetan Plateau lake ecosystems - Jianan Zheng; Rong Wang; Yu Zhao; Kexin Zhu; Yanjie Zhao; Yuan Li; Ke Zhang; Hao Long; Ji Shen (Quaternary Science Reviews, 2026)

A novel closed-loop path planning algorithm for unmanned surface vessel swarms based on potential field-guided deep Q-learning - Chunhan Zhang; Rong Zhen; Yu Zheng; Yan Zhang; Jialun Liu; Ke Zhang; Chunxu Li (Ocean Engineering, 2026)

Layered manure facilitates phosphorus mobilization mediated by putative keystone taxa among phoD-harboring bacteria - Linkang Chen; Rong Huang; Xiaoyan Tang; Bo Kang; Yijian Zheng; Zongjin Zhang; Changquan Wang; Bing Li (Applied Soil Ecology, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Profiling hydrophobic organic pollutants in serum from vulnerable populations in Dalian, China - Yubing Dai; Ningbo Geng; Dongying Zheng; Jing Jin; Xianbo Lu; Rong Cao; Haijun Zhang; Jiping Chen (Environmental Pollution, 2026)

Novel prenylated diketopiperazines with anti-osteoclastogenic activity from the deep-sea-derived Penicillium limosum ZEN48 - Yong Zhang; Yan-Qing Guo; You Li; Zheng-Biao Zou; Zhe-Wen Chen; Rong Zhao; Robert J. Capon; Tai-Zong Wu; Chun-Lan Xie; Xian-Wen Yang (Marine Life Science & Technology, 2026)
A systematic chemical investigation of the deep-sea-derived fungus Penicillium limosum ZEN48 resulted in the isolation of four new indole-diketopiperazine alkaloids, limopiperazines A–D ( 1 – 4 ), alongside 16 known analogues ( 5 – 20 ). The structures of the new compounds were determined through comprehensive spectroscopic analysis, quantum chemical calculations, X-ray crystallography, and biogenetic considerations. Limopiperazine C ( 3 ) potently inhibited osteoclast differentiation and disrupted actin ring formation. Integrated RNA sequencing, RT-qPCR and molecular docking revealed that limopiperazine C exerts the anti-osteoclastogenic effect by modulating the ferroptosis signaling pathway via targeting heme oxygenase-1 (Hmox-1), positioning it as a promising lead compound for developing anti-osteoporotic agents.

Protective Effects of Carvacrol Against Vibrio harveyi Infection in Sebastes schlegelii and Its Underlying Mechanisms - Tianwei Wang; Yongxiang Yu; Chunyuan Wang; Yingeng Wang; Zhiqi Zhang; Xiaojun Rong; Meijie Liao; Kun Hu; Zheng Zhang (Fishes, 2026)
The inappropriate use of antibiotics in aquaculture has exacerbated antimicrobial resistance in pathogens, thereby reducing the efficiency of aquaculture production. Therefore, it is crucial to develop effective antibiotic alternatives capable of inhibiting pathogenic bacteria. Against this background, the present study investigated the efficacy and underlying mechanism of carvacrol against Vibrio harveyi in the mariculture of the marine fish Sebastes schlegelii, aiming to provide data support for the development of green fishery drugs to replace antibiotics. The results indicated that pre-treatment with carvacrol increased the survival rate of infected S. schlegelii. Meanwhile, post-infection administration of carvacrol alleviated intestinal pathological damage. Carvacrol regulated host immunity by modulating the transcription of the immune-related genes NF-κB/RelA and IL-15. Carvacrol did not significantly alter the activities of SOD, MDA, or CAT, suggesting that the oxidative defense pathway was not primarily involved. Analysis of intestinal Vibrio load confirmed that carvacrol could inhibit the growth and colonization of intestinal Vibrio, thereby maintaining microbial homeostasis. Immunohistochemistry and peripheral blood flow cytometry showed that carvacrol enhanced the adaptive immunity of fish by increasing the proportions of CD4-1+ T cells and CD79a/CD79b+ B cells in tissues and peripheral blood. In conclusion, carvacrol enhances the resistance of S. schlegelii against V. harveyi by inhibiting pathogenic bacteria, improving intestinal morphological structure, reducing pathogenic bacterial load to maintain microbial homeostasis, and enhancing the adaptive immunity of the organism. This study provides a theoretical basis and data support for the substitution of antibiotics and the development of green feed additives in aquaculture.

A multicomponent Fc-fused subunit vaccine induces cross-protective immunity against porcine reproductive and respiratory syndrome virus QYYZ-like and NADC30-like strains - Linxing Tian; Zhengdan Lin; Mengxi Pan; Yanwen Wen; Mingxing Lu; Shudan Liu; Chao Zhang; Zhenxiang Rong; Jiahui Ma; Ruiqu Zhou; Nan Cao; Xinghua Chen; et al. (Veterinary Microbiology, 2026)

A germline-specific vesicular structure licenses mRNA activation during spermiogenesis and is hijacked in gastric cancer - Mingxi Liu; Zerui Wang; Yinuo Li; Qingsong Xie; Zhuang Xiao; Xuezhi He; Guanxiong Wang; Yang Gao; Yini Zhang; Lin Zheng; Xun Xia; Lujie Chen; et al. (Science Bulletin, 2026)

An arabinogalactan from Bupleurum chinense DC. attenuates LPS-induced inflammation in RAW264.7 macrophages - Bowen Zheng; Chenxu Jiang; Zheng Wang; Qiuhong Zhang; Hang Du; Nana Huang; Jin Wang; Jinhua Du; Daizhou Zhang; Rong Sun; Daijie Wang (Carbohydrate Polymers, 2026)

Metabolic reprogramming by baicalein disrupts fibroblast–macrophage crosstalk in idiopathic pulmonary fibrosis - Wen Zhang; Liu-Liu Yuan; Jia-Rong Li; Tian-Sheng Zheng; Li-Hong Fan (Chemico-Biological Interactions, 2026)

Design, synthesis, biological evaluation, and computational studies of chalcone scaffolds as cholinesterase inhibitors - Xue-Wei Zhou; Yi-Xuan Wang; Wen-Rong Du; Chao-Yue Zhang; Shi-Hao Qin; Zheng-Yue Ma (Medicinal Chemistry Research, 2026)

ANKFN1 in skin fibroblasts may modulate mast cell activity and is associated with dupilumab response in atopic dermatitis - Qiu-ju Wei; Jia-rong Lu; Wan-yan Xiang; Hai-qi Liang; Si-qi Zhang; Si-yu Huang; Jun-wen Peng; Ze-feng Zhou; Qiu-ju Li; Wen-jun Zheng (Immunologic Research, 2026)

Cloning, heterologous expression, and characterization of a metagenome-derived GH10 xylanase with salt and alkali tolerance from Xinjiang saline-alkali soil - Jing Gao; Hua-Lin Li; Mao-Song Li; Zong-Jin Shao; Zheng-Feng Yang; Chan-Jin Li; Zhi-Xin Zhang; Dan Zhu; Zhi-Hua Lv; Rong-Huan Song; Jian-Ling Li; Wei Hu; et al. (Antonie van Leeuwenhoek, 2026)

Design, synthesis, characterization and exploration of anti-HBV activity of matrine-adenine hybrids - Meng-Fan Xie; Zhou-Fei Zheng; Jing-Lei Wang; Rong-Tao Li; Zhi-Jun Zhang (Molecular Diversity, 2026)

Corrigendum to “Flooding duration affects the temperature sensitivity of soil extracellular enzyme activities in a lakeshore wetland in Poyang Lake, China” [Sci. Total. Environ., Volume 874 (2023), 162397] - Xingyun Huang; Kexin Wang; Xiuting Wen; Jie Liu; Yan Zhang; Jun Rong; Ming Nie; Chun Fu; Bofu Zheng; Zhifen Yuan; Ruichang Shen (Science of The Total Environment, 2026)

Impact of organic carbon composition on bacterial community assembly in organic and mineral soil layers under phosphorus addition in a Robinia pseudoacacia plantation - Ahejiang SAILIKE; Yujie LIANG; Rong FU; Hongjian HAO; Rong WANG; Ning PENG; Shicai LI; Zhouchang YU; Fangxin ZHENG; Wei ZHANG; Yangyang LIU; Peizhi YANG; et al. (Pedosphere, 2026)

The effects of water depth, temperature and seasonal water-column overturning on sediment-derived odorous volatile organic compounds of a ladder-step reservoir, Yiwu, China - Bo Gao; Junyu Ma; Jiahe Wang; Hongbin Zhu; Yangkang Fang; Qinggang Gong; Zhizheng Luo; Yi He; Rong Zhang; Cancan Jiang; Yongzhi Chi; Yanghui Xiong; et al. (Journal of Environmental Chemical Engineering, 2026)

A room-temperature wireless NO2 gas sensor enabled by WO3 modified V2CTx nanosheets - Haineng Bai; Rui Guo; Yixin Zhou; Cheng Feng; Yiru Chen; Shengjie Zhang; Yamin Feng; Weifeng Liu; Kuili Liu; Fuqiang Guo; Jin Wang; Dunjun Chen; et al. (Chemical Engineering Journal, 2026)

Food sources of the Synaptid Protankyra bidentata and its trophic competition with the sea cucumber Apostichopus japonicus in culture ponds - Jianlong Ge; Teng Lu; Jinjin Wang; Meijie Liao; Xiaojun Rong; Bin Li; Yingeng Wang; Yongxiang Yu; Chunyuan Wang; Zheng Zhang; Zhiqi Zhang (Aquaculture, 2026)

cGAS-STING activation mediated by FAM83H-AS1/HMGB1 elicits NF-κB-dependent immune evasion in breast cancer - Zhi-Mei Liang; Lili Lin; Shu-Rong Li; Xin-Yu Ma; Wenda Zhang; Na-Na Li; Zheng-Hao Lai; Guorun Liang; Wei Zhao; Yiming Zhao; Man-Li Luo (Science Bulletin, 2026)

RBOHC-derived ROS control plant nitrate starvation response via WRKYs-activated expression of high-affinity nitrate transporters - Tian Yuan; Meng-Qi Cui; Chen Xu; Jing-Ying Yan; Wo-Na Ding; Ji-Ming Xu; Yun-Rong Wu; Gui-Xin Li; Yu Liu; Dong Zhang; Chuan-Zao Mao; Moussa Benhamed; et al. (Science Bulletin, 2026)

FabH (β-Ketoacyl-ACP Synthase III) -- Promising Novel Antibacterial Target and Its Inhibitors - Gui-Wen Li; Qing-Yun Rong; Wen Zhang; Guo-Wu Rao; Quan Zheng (Medicinal Chemistry Research, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Estimating soil moisture at farm scale with high spatial resolution: integrating remote sensing data, and machine learning - Di Wang; Shenhan Xu; Shuai Wang; Wenhui Liu; Nanjuan Zheng; Zhen Wang; Yao Rong; Chenglong Zhang; Chaozi Wang; Nigenare Amantai; Zailin Huo (Journal of Hydrology, 2026)

Engineering dual defects onto graphitic carbon nitride nanosheets enables outstanding performance for photodegradation of microcystin-LR - Ziqi Deng; Wenqing Zhang; Liangjie Shen; Lei Shi; Xiang Zheng; Jianzhong Zheng; Rong Cheng (Journal of Environmental Sciences, 2026)

Boosting surface basicity of In2O3 aerogel for high-performance H2S sensors via an in-situ annealing strategy of carbon-composited In(OH)3 - Zheng Yang; Qian Rong; Wei Zhang; Qi Xu; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2026)

Hydroxybutyl chitosan-based thermosensitive hydrogel enhanced osteoporotic bone regeneration through sustained release of alendronate and BMP-2 - Mingyuan Lei; Haibing Liu; Qiang Zhong; Libo Zhao; Jingwen Liu; Huaming Mai; Yuheng Zhang; Hongyu Wang; Yourong Chen; Rong Chen; Yixin Xu; Hao Li; et al. (Carbohydrate Polymers, 2026)

Low-δ18O magmas at Batur, Indonesia: Evidence for slab-window melting beneath arc volcanoes - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2026)

Plant-soil feedback driven by root-associated fungal communities accelerates the secondary succession of bare saline-alkaline grassland patches - Xiaona Zheng; Yuhong Yin; Dan Yang; Jingjuan Bi; Wenlong He; Siya Li; Xiao Liang; Jigui Chen; Rong Wang; Zhiying Guo; Xing Li; Tao Zhang; et al. (Plant and Soil, 2026)

Trace element zoning and temperature variation in sphalerite from the giant Nannihu porphyry-skarn-epithermal polymetallic system, central China - Chang Wang; Zhan-Ke Li; Ioan Sanislav; Yi Zheng; Xiao-Ming Li; Rong-Zhen Zhang; Jia Hu; Jun Zhang (Mineralium Deposita, 2026)

A novel mechanistic insight into CO2 effects on chain elongation in Clostridium kluyveri based on transcriptomic and ¹³C-targeted metabolomic analyses - Weizhong Huo; Rong Ye; Tong Hu; Yuchao Shao; Zelin Zheng; Ruifu Zhang; Wenjing Lu; Qirong Shen (Water Research, 2026)

Contrasting impacts of wheat rhizosphere and hyphosphere on methane and nitrous oxide emissions under straw incorporation - Baowei Huang; Yongcheng Wu; Zheng-Rong Kan; Fede Berckx; Petra Fransson; Qian Zhang; Feng-Min Li; Martin Weih; Haishui Yang (Soil and Tillage Research, 2026)

Synergistic plant-microbe interactions enhance the removal of metolachlor and acephate: kinetics and biological response mechanisms - Liping Zhao; Yucong Zheng; Mawuli Dzakpasu; Dongxian Zhang; Zhuanzhuan Sun; Xinyu Ma; Yunze Chai; Luyao Zhang; Rong Chen (Journal of Water Process Engineering, 2026)

Constructed wetland substrate–mediated stereoselective transformation of metolachlor: Influence of redox conditions and microbial community dynamics - Liangjin Chen; Yucong Zheng; Mawuli Dzakpasu; Qian Yang; Guochen Liu; Liping Zhao; Tianfu Wu; Dongfu Zhang; Xiaochang Wang; Rong Chen (Environmental Research, 2026)

Synchronously interfacial fire retardancy and mechanical strengthening of glass fiber nylon 6 by temperature-responsive coupling agent - Han Li; Zhi Li; Rong Kuai; Wei-Zheng Zhang; Yanhao Huang; Qing-Wen Zeng; Zhi Hu; De-Yi Wang (Chemical Engineering Journal, 2026)

Corrigendum to “a sandwich-structured anisotropic conductive film with robust interfacial reliability and conductivity for functional electrical interconnections” [chemical engineering journal 505 (2025): 159721/CEJ_159721] - Yang Liu; Yan Pan; Zeyu Zheng; Hebin Zhang; Rong Sun; Pengli Zhu (Chemical Engineering Journal, 2026)

An intelligent nanotheranostic for size-driven integrated tumor radiosensitization and radioprotection - Mengting Gao; Yarong Jin; Xiaorui Song; Jian Zhang; Ajing Wu; Qiao Ye; Binyue Zhang; Jinxuan Li; Rong Dai; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2026)

Systematic investigation, expression analysis of TCP transcription factors in eggplant and functional characterization of SmTCP3 gene involved in response to drought stress - Fa-xiang Wan; Yu Zheng; Rong-rong Li; Ying-fan Zhang; Hua-ju Zheng; Ji-qing Li; Yi-min Jiang; Jia-rui Yang; Bo Qi; Jun Gao; Ya-nan Chen; Yu Pan (Genetic Resources and Crop Evolution, 2026)

Rare earth element hyperaccumulation in vascular plants: Occurrence, mechanisms, and applications - Ruo-Rong Liu; Cui-Ling Huang; Hong-Xiang Zheng; Chong Liu; Rui-Qi Zhang; Yue Cao; Antony van der Ent; Can-Die Xie; Wen-Shen Liu; Jean Louis Morel; Catherine Sirguey; Damien Blaudez; et al. (Critical Reviews in Environmental Science and Technology, 2025)

Advancements in urban water management and ecological restoration technologies: Frameworks, challenges, and emerging trends - Sitong Zou; Yucong Zheng; Mawuli Dzakpasu; Qian Li; Ting Cao; Liping Zhao; Tianfu Wu; Dongfu Zhang; Yunze Chai; Rong Chen (Journal of Water Process Engineering, 2025)

Field verification of the surface renewal method for evapotranspiration measurement in arid agricultural area: The uncertainty of calibration parameter - Zhen Wang; Nanjuan Zheng; Bingbing Jiang; Yao Rong; Xin Li; Peijin Wu; Weishu Wang; Chenglong Zhang; Zailin Huo (Journal of Hydrology, 2025)

Engineering sulfoxide synthases for efficient microbial production of ergothioneine: Mechanisms, strategies, and perspectives - Xiaodi Wei; Lijuan Liu; Sheng Dong; Pingle Wu; Xiao Zhang; Min Yang; Rong Zheng; Haibo Zhang (Food Chemistry, 2025)

Structural characterizations and potential delivery platform of glucan dendrimer-derived hydrogel - Jingyi Zheng; Rong Zhou; Zhengyu Jin; Tao Zhang; Ming Miao (Carbohydrate Polymers, 2025)

Environmental Filtering Drives Taxon Homogenisation and Threatens Freshwater Biodiversity in Southwest China - Wenxiu Zheng; Yanjie Zhao; Hui Yang; Enlou Zhang; Rong Wang (Journal of Biogeography, 2025)
Aim Understanding the mechanisms shaping biodiversity patterns, particularly the role of community assembly processes, remains a central challenge in ecology. In this study, we examine how climate and anthropogenic pressures jointly drive community assembly and biodiversity patterns through taxon co‐occurrence analyses. Location Southwest China, East Asia. Taxa Chironomids. Methods Spatial chironomid data from 129 lakes (3297‐m elevational gradient) across southwest China and a century‐scale subfossil chironomid record from an alpine lake, Tiancai, were used to assess taxon co‐occurrence and biodiversity patterns across space and time, and linked to environmental drivers including climate and human impact. Results Spatially, chironomid richness exhibited a unimodal elevational pattern, peaking at mid‐elevations (3011–4014 m a.s.l.) where co‐occurrence was minimised; conversely, both low‐ (1291–2988 m a.s.l.) and high‐ (4022–4588 m a.s.l.) elevation lakes showed reduced richness and elevated co‐occurrence. It shows that key environmental proxies diverged, that is, human activity intensity, temperature and nutrient level declined with elevation, water transparency increased while productivity and environmental heterogeneity peaked mid‐elevations. Temporally, at mid‐elevation Lake Tiancai, richness declined since the 1990s while co‐occurrence, evenness and variability increased, driven predominantly by rising temperature, with rare taxa and specialists accounting for the vast majority of taxon loss. Conclusions Our findings reveal elevation‐dependent biodiversity mechanisms: Human disturbance dominates richness patterns in low‐elevation lakes, while climate warming disproportionately threatens rare and narrowly distributed taxa at mid‐elevations. Critically, an inverse richness‐co‐occurrence relationship persists across spatial (low/mid elevations) and temporal scales, where elevated co‐occurrence signals environmental filtering that constrains local biodiversity. Conservation strategies must, therefore, prioritise protecting heterogeneous habitats to mitigate biotic homogenisation and sustain vulnerable taxa.

Exploring the molecular mechanism of Epichloë gansuensis in enhancing the tolerance of Achnatherum inebrians to nitrogen deficiency stress - Ronggui Liu; Hanwen Zhang; Beichen Wang; Jie Jin; Chao Xia; Kamran Malik; Yang Yang; Rong Zheng; Chao Wang; Jianfeng Wang (Mycological Progress, 2025)

Unveiling the gut-vascular connection: Gut microbiota regulates cardiovascular toxicity induced by combined exposure to PM2.5 and high-fat diet via butyric acid/NLRP3 pathway - Jiayu Tian; Jiaji Cheng; Huan Yang; Zeyu Niu; Lifang Zhao; Linlin Guan; Nannan Liu; Shuling Rong; Caihong Wang; Dongxing Shi; Huiqiu Zheng; Na Cao; et al. (Journal of Hazardous Materials, 2025)

Morphology and nutrient content of bamboo rhizomes: Responses to enclosure succession in a Phyllostachys edulis forest in Wuyi Mountains, China - Xing Cai; Rui Cheng; Zhenhua Chen; Jiannan Lin; Min Wu; Jiaying Liu; Jihong Xiao; Yuchen Lin; Lingyan Chen; Yirong Zhang; Jundong Rong; Tianyou He; et al. (Forest Ecology and Management, 2025)

The multimodal anti-tumor effect of cisplatin nanoparticles loaded with bacterial antibodies in combination with radiotherapy: targeting hypoxic tumor and reshaping of the immune microenvironment - Min Wu; Zhouxue Wu; Weizhou Wang; Yunxue Zheng; Hongxia Li; Yuan Huang; Liping Deng; Yingqi Gu; Jinfeng Rong; Xiaoyin Zhang; Wen Yang; Yue Chen; et al. (Chemical Engineering Journal, 2025)

Gut microbiota-metabolite dynamics in Sebastes schlegelii following Vibrio harveyi infection - Yindong Gu; Yongxiang Yu; Chunyuan Wang; Yingeng Wang; Zhiqi Zhang; Xiaojun Rong; Meijie Liao; Lei Qin; Bin Li; Zheng Zhang (Aquaculture International, 2025)

Anthraquinone-2,6-disulfonate (AQDS) modified bio-cathode stimulated chain elongation process in electro-fermentation systems for caproate production - Weizhong Huo; Rong Ye; Zelin Zheng; Jing Yu; Zhaofan Lin; Ruifu Zhang; Qirong Shen (Journal of Environmental Chemical Engineering, 2025)

Adaptive responses and molecular mechanisms of Lactiplantibacillus plantarum to citric acid stress - Han Xie; Wei Zhang; Cong-Rong Shi; Rui-Shan Liu; Zhen-Ming Lu; Li-Juan Chai; Hong-Yu Xu; Jin-Song Shi; Xiao-Juan Zhang; Zheng-Hong Xu (International Journal of Food Microbiology, 2025)

A ZnO packaged MEMS hydrogen sensor for reliable SIBO breath analysis with anti-H2S interference - Zheng Yang; Qian Rong; Wei Zhang; Xintao Fan; Mengen Shao; Jiang Li; Chunchang Wang; Youmin Guo (Chemical Engineering Journal, 2025)

Adipose-bone microenvironment precision-regulation nanoplatform: A visualized mild photothermal-enhanced osteogenesis strategy for osteonecrosis of the femoral head - Jinxuan Li; Mengting Gao; Yuhang Wang; Rong Dai; Qi Liu; Shutong Wu; Jian Zhang; Hua Wu; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2025)

Residual polyacrylamide-induced membrane fouling in short-flow coagulation-ultrafiltration: Behavior and mechanism - Mohan Wei; Yaozhong Zhang; Xing Zheng; Chi Zhang; Jiheng Duan; Kai Guo; Menghan Wang; Dongfei Li; Tianshuo Huang; Rong Chen (Chemical Engineering Journal, 2025)

Construction of LncRNA-miRNA-mRNA regulatory network in IgA nephropathy mice model by RNA-sequencing and bioinformatics analysis - Wen Jia Zheng; Tao Liu; Xiao Li Zhu; Yu Ting Zhang; Liang Bing Wei; Ya Chen Gao; Xing Xing Zhuang; Jia Rong Gao (Genes & Genomics, 2025)

Common bean milk or yogurt prevents low-grade chronic inflammation and associated metabolic disorders in a mouse model - Yuhuan Chen; Hua Zhang; Dion Lepp; Shilian Zheng; Ronghua Liu; Zeyuan Deng; Yoshinori Mine; Peter Pauls; Rong Tsao (Food Bioscience, 2025)

Hydrogel pads loaded with essential oil contribute to maintaining blueberry quality after transportation - Yuxuan Li; Haifeng Rong; Sixu Lin; Yaohui Zheng; Ling Yang; Bingxin Sun; Yunhe Zhang; Yufeng Xu; Xuerui Yan (Food Packaging and Shelf Life, 2025)

Unraveling the effect of sorbitol on Cu-based catalysts for the continuous hydrogenation of CO2-derived ethylene carbonate to methanol and ethylene glycol - Tong-Yang Song; Ji-Zheng Zhang; Jun He; Xian-Lang Chen; Xin-Yuan Huang; Ai-Ping Jia; Xiaohong Li; Rong-Rong Li; Ji-Qing Lu (Chemical Engineering Journal, 2025)

Biomembrane delivers neurotrophic factor for spinal cord injury recovery through microneedle patch - Bowen Zheng; Mingpai Ge; Jing Zhang; Tao Zhu; Yu Yi; Hongtao Rong (Chemical Engineering Journal, 2025)

Carbon encapsulated Fe0/Fe oxides for heterogeneous electro-Fenton process: Promoting Fe(II) regeneration under nanoconfinement - Kun-Xiao Zhang; Ablajan Tunyaz; Guan-Nan Zhou; Rong-Rong Ding; Pei-Wen Zheng; Xiao-Cheng Liu; Hou-Yun Yang; Yang Mu (Chemical Engineering Journal, 2025)

Beyond convention: Construction of β-cyclodextrin-based shape-changing particles capable of light-responsive control and bioactivity application - Pu-Ying Qi; Li-Hong Shi; Zhi-Cheng Zheng; Yu-Mei Feng; Tai-Hong Zhang; Rong-Shuang Luo; Shuai Tan; A-Ling Tang; Hou-Yun Huang; Xiang Zhou; Hong-Mei Xiang; Li-Wei Liu; et al. (Carbohydrate Polymers, 2025)

6-Methoxydihydrosanguinarine Suppresses the Proliferation of Non-small Cell Lung Cancer Cells through Elevation of ROS and Activation of IRE1/JNK Signaling - Xiao Qi; Chong Niu; Zi-zheng Zhang; Meng-ru Chen; Feng-ze Wang; Hong-rong Fei (Cell Biochemistry and Biophysics, 2025)

Implementation and topological characterization of Weyl exceptional rings in quantum-mechanical systems - Hao-Long Zhang; Pei-Rong Han; Xue-Jia Yu; Shou-Bang Yang; Jia-Hao Lü; Wen Ning; Fan Wu; Qi-Ping Su; Chui-Ping Yang; Zhen-Biao Yang; Shi-Biao Zheng (Science Bulletin, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Automatic morphologic classification of Martian craters using imbalanced datasets of Tianwen-1’s MoRIC images with deep neural networks - Qifang Zheng; Rong Huang; Yusheng Xu; Fangzhao Zhang; Changjiang Xiao; Luning Li; Xiaohua Tong (Planetary and Space Science, 2025)

A novel approach to water-salt migration prevention: foamed lightweight soil barrier layer technology - Yang Zhao; Zheng Lu; Jie Liu; Chuxuan Tang; Abdollah Tabaroei; Rong Zhang; Yinuo Feng; Hailin Yao (Cold Regions Science and Technology, 2025)

Spatio-temporal dynamic characteristics of the substitution effect of ride-hailing travel and its multi-activity network: a case study of Chengdu - Zhicheng Zheng; Yang Li; Peijun Rong; Lijun Zhang; Yaochen Qin; Gangjun Liu (Journal of Transport Geography, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Semaphorin 3A protects against thoracic aortic aneurysm dissection by suppressing aortic angiogenesis - Li-Fei Wu; Jiao-Jiao Zhang; Xing Zhang; De-Ping Wang; Zhi-Fa Zheng; Jing Shen; Ying Zhou; Li-Juan Gao; Xuan Shang; Jun-Ya Ning; Qing-Hua Liu; Lan Zhou; et al. (Angiogenesis, 2025)

Autonomous collision avoidance decision-making method with human-like attention distribution for MASSs based on GMA-TD3 algorithm - Wuyue Rong; Jian Zheng; Yang Chen; Yang Liu; Zekun Zhang (Ocean Engineering, 2025)

The long-term dynamics of biodiversity and stability of the diatom community under climate warming in a Tibetan alpine lake - Yanjie Zhao; Rong Wang; Hengshuai Qiu; Wenxiu Zheng; Enlou Zhang; Xiangdong Yang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Regulating the gradient water distribution via hydro-philic/phobic compositional design in ionogels for stable zinc ion batteries - Rong Zheng; Nan Jiang; Baojun Wang; Chengyi Hou; Qinghong Zhang; Hongzhi Wang; Yaogang Li; Kerui Li (Chemical Engineering Journal, 2025)

Gut microbiota and serum metabolomics unveil the role of Phellinus ribis polysaccharides in improving Alzheimer's disease symptoms in senescence-accelerated mice - Zhiyuan Zhang; Shuai Wang; Rong Rong; Guoying Zhang; Zheng Li; Yuanyuan Li; Rongxiang Wang; Yuhong Liu; Kejian Li (Metabolic Brain Disease, 2025)

Atmospheric nitrogen deposition has minor impacts on the abundance and diversity of arbuscular mycorrhizal fungi and their contribution to soil carbon stock in tropical forests - Andi Li; Peter Meidl; Senhao Wang; Bo Tang; Matthias C. Rillig; Guangcan Yu; Jing Chen; Rongzhen Liu; Zhiyang Lie; Anchi Wu; Lili Rong; Cheng Peng; et al. (Soil Biology and Biochemistry, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

A millennial record of lake ecosystem responses to climatic variability in the Yellow River Source Area - Jianan Zheng; Rong Wang; Hanxiao Zhang; Shouliang Huo; Jingjing Li; Yanjie Zhao; Ji Shen (Quaternary Science Reviews, 2025)

Simulated microgravity activates autophagy expression in the rat retina - Meng Liu; Yuyu Wang; Fei Ren; Wenqian Zhang; Hanwen Zheng; Rong Zhang; Caiyun Gao; Ling Luo; Chuang Nie; Jianwen Gu (Life Sciences in Space Research, 2025)

Combination of extrusion and bamboo leaf flavonoids modulates in vitro maize starch digestion: Insight into the molecular mechanisms and multi-scale structure - Jiong Zheng; Rong Hu; Yuming You; Xiaojing Li; Fusheng Zhang; Liangru Wu (Food Chemistry, 2025)

Unraveling the impact of micro- and nano-sized polymethyl methacrylate on gut microbiota and liver lipid metabolism: Insights from oral exposure studies - Peng Chen Zheng; Xin Qiang Pan; Yi Jiong Zhou; Keng Po Lai; Rong Li; Xiao Xi Zhang (Environmental Pollution, 2025)

Full realization of the RIBLL2 separator at the HIRFL-CSR facility - Xiao-Dong Xu; Yong Zheng; Zhi-Yu Sun; Yu-Nan Song; Bao-Hua Sun; Satoru Terashima; Chang-Jian Wang; Ge Guo; Guang-Shuai Li; Xiu-Lin Wei; Jun-Yao Xu; Ji-Chao Zhang; et al. (Science Bulletin, 2025)

Vertical distributions of dimethyl sulfide and dimethylsulfoniopropionate and impacts of DMSP lyase and bacteria in the Yellow Sea and East China Sea - Xin-Ran Song; Qian-Yao Ma; Juan Yu; Gui-Peng Yang; Rong Chen; Zheng-Yu Zhang; Yu Jiang; Long-Fei Liu (Marine Environmental Research, 2025)

The promotional effect of MoO3 on the CeO2/TiO2 catalyst for simultaneous removal of NO and toluene: From the insights of experimental and DFT studies - Zhuang Hu; Yi-fei Yu; Hai-yuan Zhao; Zheng-long Wu; Rong Guo; Jia-le Zhou; Xin-yue Zhou; Bing Zhang; Yang-wen Wu; Li Zhao; Qiang Lu (Journal of Environmental Chemical Engineering, 2025)

A comparative study of four color measurement methods for soil color identification and related properties prediction - Yuanyuan Du; Fengjin Kang; Zhangke Huang; Luyi Wang; Ya Zhang; Decheng Li; Guanghui Zheng; Rong Zeng (Computers and Electronics in Agriculture, 2025)

Herbaceous competition does not affect positive tree diversity effects on seedling crown complementarity - Muhammad Abdullah; Li-Ting Zheng; Li Zhang; Bai-Yu Yang; Xiao-Chen Fang; Di-Feng Bao; Samreen Ghulam Rasool; Ci-Liang Zhao; En-Rong Yan (Forest Ecology and Management, 2025)

Nanometabolomics elucidated biological response of 3D printed vascular stents: Towards metabolic reprogramming of metabolome and lipidome - Yu Zeng; Yumeng Liu; Tong Sun; Ge Liang; Luolan Gui; Wen Zheng; Lu Zhang; Yuanping Gao; Yunfei Dang; Rong Fan; Yang Lu; Dingkun Zhang; et al. (Chemical Engineering Journal, 2025)

Seasonal variations in the soil microbiota of a temperate wetland in Northeast China in response to nitrogen deposition - Rong-Tao Zhang; Shen-Zheng Wang; Hai-Xiu Zhong; Xin Sui; Ying-Nan Liu (CATENA, 2025)

Substrate preference triggers metabolic patterns of indigenous microbiome during initial composting stages - Yi Ren; Chen Liu; Jiayu Luo; Xuhui Deng; Daoyue Zheng; Jiahui Shao; Zhihui Xu; Nan Zhang; Wu Xiong; Hongjun Liu; Rong Li; Youzhi Miao; et al. (Bioresource Technology, 2025)

Opposing island biogeographic effects of turnover and nestedness on beta-diversity of soil faunal communities between woodland and deforested grassland - Zengyan Li; Zengke Zhang; Anna Yang; Sufeng Pan; Junyong Zheng; Ling Mou; Wensheng Chen; Tian Zhang; Liyi Zhou; Wenhui You; David A. Wardle; En-Rong Yan (Applied Soil Ecology, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A sandwich-structured anisotropic conductive film with robust interfacial reliability and conductivity for functional electrical interconnections - Yang Liu; Yan Pan; Zeyu Zheng; Hebin Zhang; Rong Sun; Pengli Zhu (Chemical Engineering Journal, 2025)

Nicotinamide riboside restores nicotinamide adenine dinucleotide levels and alleviates brain injury by inhibiting oxidative stress and neuroinflammation in a mouse model of intracerebral hemorrhage - Jing She; Hua Zhang; Hui Xu; Yan-Yan Li; Jun-Chao Wu; Rong Han; Fang Lin; Yan Wang; Rui Sheng; Jin-hua Gu; Zheng-Hong Qin (Molecular Neurobiology, 2025)
Hemorrhagic stroke is a global health problem owing to its high morbidity and mortality rates. Nicotinamide riboside is an important precursor of nicotinamide adenine dinucleotide characterized by a high bioavailability, safety profile, and robust effects on many cellular signaling processes. This study aimed to investigate the protective effects of nicotinamide riboside against collagenase-induced hemorrhagic stroke and its underlying mechanisms of action. An intracerebral hemorrhage model was constructed by stereotactically injecting collagenase into the right striatum of adult male Institute for Cancer Research mice. After 30 minutes, nicotinamide riboside was administered via the tail vein. The mice were sacrificed at different time points for assessments. Nicotinamide riboside reduced collagenase-induced hemorrhagic area, significantly reduced cerebral water content and histopathological damage, promoted neurological function recovery, and suppressed reactive oxygen species production and neuroinflammation. Nicotinamide riboside exerts neuroprotective effects against collagenase-induced intracerebral hemorrhage by inhibiting neuroinflammation and oxidative stress.

Analysis of factors influencing microseismic detection and location in shale gas extraction areas of western Hubei - Wan-peng Hao; Li-fen Zhang; Yan-nan Zhao; Rong-ying Zheng; Wei-bing Qin; Jing-gang Li (Applied Geophysics, 2025)

Identification of Boveria labialis parasitism in the respiratory tree of the Cultured Sea cucumber, Apostichopus japonicus - Wenyue Hao; Xiaojun Rong; Meijie Liao; Bin Li; Yingeng Wang; Jianlong Ge; Jinjin Wang; Zheng Zhang; Yongxiang Yu (Aquaculture, 2025)

The key pathogenic factor GcSP2 of Geotrichum citri-aurantii plays an important role in disrupting citrus metabolism and immunity - Rong Liu; Haoxiang Zheng; Di Wang; Haijue Zhang; Yan Wu; Xue Li; Zhengfeng Liu; QingJun Kong; Xueyan Ren (Postharvest Biology and Technology, 2025)

Effective periodate activation of direct Z-scheme g-C3N4/Cu2O heterojunction for photocatalytic norfloxacin degradation, anti-bacterial activity and toxicity assessment - Qinyi Gu; Jian Rong; Yuzhe Zhang; Xudong Zheng; Ziyao Zhou; Zhongyu Li; Song Xu (Chemical Engineering Journal, 2025)

Bismuth/manganese-doped carbon dots in calcium phosphate matrix: Dynamic conformational nanoparticles enhancing tumor accumulation, deep penetration, and radiosensitivity - Jiahao Liu; Qingnian Li; Hanyu Tu; Jie Feng; Xiaofei Fan; Ze Mi; Hongpei Han; Xiaoqian Ma; Qi Liang; Zheng Zhang; Hongshuai Hou; Pengfei Rong; et al. (Chemical Engineering Journal, 2025)

Global techno-economic analysis of MBR for hospital wastewater treatment - Junqing He; Zhenxing Zhang; Fangnan Cui; Xue Tan; Xiang Zheng; Rong Cheng (Science of The Total Environment, 2024)

A tumor-pH-responsive phthalocyanine as activatable type I photosensitizer for improved photodynamic immunotherapy - Ling Zhang; Rong-Bin Que; Ting-Ting Ke; Chao Wang; Wei Xie; Hong-Jie Sun; Bi-Yuan Zheng; Mei-Rong Ke; Jian-Dong Huang; Xingshu Li (Journal of Photochemistry and Photobiology B: Biology, 2024)

Variation profiles, formation mechanisms, and emission risks of brominated flame retardant compounds during cement kiln co-processing of hexabromocyclododecane-containing waste - Xin Li; Yahui Liu; Bingcheng Lin; Guohua Zhu; Jian Wang; Xiao Wang; Yueyao Yang; Shanshan Zhang; Guorui Liu; Rong Jin; Minghui Zheng (Journal of Hazardous Materials, 2024)

MOF-derived S, N co-doped porous carbon matrix with single Fe atoms and CoSx nanoparticles dual-sites for enhanced oxygen reduction - Yu chen; Jian Rong; Jing Wu; Yuzhe Zhang; Huaisheng Ao; Xudong Zheng; Chao Jing; Ruilan Yang; Ziyao Zhou; Zhongyu Li (Chemical Engineering Journal, 2024)

Cohort Profile: TRacing Etiology of Non-communicable Diseases (TREND): Rationale, Progress and Perspective - Hui-Ying Ren; Ying Lv; Bei-Ning Ma; Chang Gao; Hong-Mei Yuan; Hai-Hong Meng; Zheng-Qian Cao; Ya-Ting Chen; Yan-Xi Zhang; Yu-Ting Zhang; Wei Liu; Yu-Ping Fan; et al. (Phenomics, 2024)
The TRacing Etiology of Non-communicable Diseases (TREND) cohort is a prospective longitudinal cohort and biobank that is mainly based in Ma’anshan, Anhui Province, China. The primary aim of the study is to decipher comprehensive molecular characterization and deep phenotyping for a broad spectrum of chronic non-communicable diseases (NCDs), which focuses on providing mechanistic insights with diagnostic, prognostic and therapeutic implications. The recruitment was initiated in 2023 and is expected to complete in 2025 with 20,000 participants originated from urban and rural area. In the first phase, 3360 participants were recruited. Follow-up visits are scheduled annually and intervally for a total of 30 years. The cohort includes individuals aged over 18 years. Two participants with first-degree linkage were recruited from a household. The age distribution of recruited participants was stratified into four categories: 18–45, 45–55, 55–65, and ≥65 years, aligning with the population proportions of Ma’anshan. Meanwhile, the gender distribution was controlled by pairing men and women from the same household. Data collected at baseline includes socio-economic information, medical history, lifestyle and nutritional habits, anthropometrics, blood oxygen, electrocardiogram (ECG), heart sound, as well as blood, urine and feces tests results. Molecular profiling includes genome, proteome, metabolome, microbiome and extracellular vesicles -omics. Blood, urine and fecal samples are collected and stored at −80 °C in a storage facility for future research.

Data mining-based identification of epigenetic signatures with discrimination potential of lung adenocarcinoma and squamous cell carcinoma - Wen-guang Pang; Min Ye; Jia-rong Chen; Liang Zhang; Zheng Wang (Molecular Biology Reports, 2024)

Simple theranostics nanoagent for precision suppression of tumor growth and metastasis: A traditional fermented product having a novel functional breakthrough - Pengmin Liu; Rong Dai; Juan Li; Lin Chen; Qi Liu; Yuhang Wang; Shichao Meng; Binyue Zhang; Jinxuan Li; Weiwei Kang; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

Molecularly tailored bifunctional nano-overlayers for efficient and stable inverted perovskite solar cells - Lu-Lu Jiang; Shao-Jie Li; Qi Li; Shuai-Ke Guo; Zhen-Rong Song; Ying-Zhuo Shen; Xiao-Nan Zhang; Dong-Sheng Zheng; Xiao-Dan Tang; Hai-Rui Liu (Chemical Engineering Journal, 2024)

Fabrication of graphene oxide/ammonium molybdophosphate composite membrane for decontamination of cesium ions from seawater - Xiao-Yi Tang; Zi-Jie Li; Lin Wang; Peng-Cheng Zhang; Kong-Qiu Hu; Li-Rong Zheng; Zhi-Hui Zhang; Li-Yong Yuan; Wang-Suo Wu; Wei-Qun Shi (Chemical Engineering Journal, 2024)

Factors associated with self-rated mental health in mothers of children and adolescents with autism spectrum disorder - Yanan Zhao; Huiyun Fan; Rong Zhang; Xiaoying Zheng (Journal of Zhejiang University-SCIENCE B, 2024)

Combined utilization of slag, fly ash, and polyacrylamide for sustainable saline soil improvement: a win-win strategy - Yang Zhao; Zheng Lu; Rong Zhang; Jie Liu; Changtao Hu; Abdollah Tabaroei; Jian Li; Tingzhou Yan; Hailin Yao (Bulletin of Engineering Geology and the Environment, 2024)

A novel hollow flower shaped Cu9S8 antibacterial agent for removing sulfonamide in water environment: effects of composite with magnetic biochar, differential adsorption, and mechanism study - Rui-peng Li; Zheng-rong Hu; Xing Wang; Jun Chen; Qing-qing Liu; Ying Zhao; Zhong-bao Zhao; Xu-lin Lu; Zhi-wei Zhang (Environmental Science and Pollution Research, 2024)

Biological exposure to microplastics and nanoplastics and plastic additives: impairment of glycolipid metabolism and adverse effects on metabolic diseases - Peng Chen Zheng; Rong Li; Keng Po Lai; Xiao Xi Zhang (Environmental Science and Pollution Research, 2024)

Influenza A Virus PB1-F2 Induces Affective Disorder by Interfering Synaptic Plasticity in Hippocampal Dentate Gyrus - Saiying Wang; Haijun Zhang; Rui Liu; Peijun Han; Qi Yang; Caiyan Cheng; Yue Chen; Zheng Rong; Chang Su; Fei Li; Gaofei Wei; Minggao Zhao; et al. (Molecular Neurobiology, 2024)

The effect on the carbon footprint of the rice-wheat system of substituting chemical fertilizers by pig manure: The results of a field experiment - Yinan Xu; Jing Sheng; Yuefang Zhang; Liping Zhang; Zheng-Rong Kan; Guofeng Sun; Jianchu Zheng (Sustainable Production and Consumption, 2024)

Preliminary analysis of the indicators and accumulation models of gas hydrates in the central Zhongjiannan Basin, western South China sea - Zhou-rong Cai; Xin Sui; Yong-jian Yao; Zheng-xin Yin; Xiao-dong Yang; Dong Ju; Rong-wei Zhu; Xiao-xiang Wang; Huo-dai Zhang (Marine and Petroleum Geology, 2024)

Constructing direct Z-scheme heterojunction of NiCo-LDH coated with g-C3N4 for boosting photocatalytic H2 evolution - Qinyi Gu; Chujun Feng; Congtian Liu; Jian Rong; Yuzhe Zhang; Xudong Zheng; Zhongyu Li; Song Xu (Fuel, 2024)

Regional-scale biogeographical patterns of soil extracellular enzyme activities across eight Chinese fir plantation locations - Han-shuo Zhang; Mi-lin Deng; Hao Yang; Bi-jiang Fang; Wen-feng Lan; Qiu-hua Ma; Huai-feng Weng; Zhi-jie Yang; Yi-rong Zhang; Yong Zheng (European Journal of Soil Biology, 2024)

Microplastics footprint in nature reserves-a case study on the microplastics in the guano from Yancheng Wetland Rare Birds National Nature Reserve, China - Huimin Jiang; Hai Cheng; Shiyue Wu; Hongshan Li; Hao Chen; Zhenghao Li; Xinyun Yao; Yanan Zhang; Yaqin Chen; Shuyi Chen; Shihao Chen; Liang Zheng; et al. (Environmental Research, 2024)

Phthalocyanine J-aggregate nanoparticles with enormous-redshifted and intense absorption: Potential structure-J-aggregation relationships and application in tumor-associated macrophages-targeted phototheranostics - Fengxiang Tang; Haodong Yu; Yanzong Huang; Xue Zhao; Zixuan Chen; Honglin Ma; Bi-Yuan Zheng; Mei-Rong Ke; Yongfan Zhang; Xingshu Li; Juyoung Yoon; Jian-Dong Huang (Chemical Engineering Journal, 2024)

A twin S-scheme CoFe2O4/VCNDA/BiVO4 nanozyme for photo-auto-enzyme-coupled catalytic degradation of carbamazepine - Chujun Feng; Qinyi Gu; Jian Rong; Xudong Zheng; Yuzhe Zhang; Qian Liang; Zhongyu Li; Song Xu (Chemical Engineering Journal, 2024)

Constructing phonon transport bridges via low-temperature sintering in Diamond@Ag/EP composite to achieve efficient 3D networks structure - Zeyu Zheng; XiaoXin Lu; Liang Xu; Yang Liu; Jianhui Zeng; Hebin Zhang; Jialin Wen; Pengli Zhu; Rong Sun; Weijing Wu (Chemical Engineering Journal, 2024)

Arc building and maturation of the Lombok Island, East Sunda Arc - Guo-Rong Tang; Wei Dan; Adi Maulana; Jian Wang; Xiu-Zheng Zhang; Yun-Ying Zhang; Xin Ma; Qiang Wang; Xi-Jun Liu; Gong-Jian Tang (Chemical Geology, 2024)

Hinokione: an abietene diterpene with pancreatic β cells regeneration and hypoglycemic activity, and other derivatives with novel structures from the woods of Agathis dammara - Zheng Wang; Zhe-Wei Yu; Yi Zhang; Wen-Hui Wang; Xin-Yi Wu; Shun-Zhi Liu; Yan-Lin Bin; Bang-Ping Cai; Shi-Yan Huang; Mei-Juan Fang; Rong Qi; Ming-Yu Li; et al. (Journal of Natural Medicines, 2024)

Composition of Sphagnum palustre L. extracts using different extraction methods - Zhi Wu; Zheng-Yi Hong; Yang Xu; Dai-Rong Wang; Qing-Bin Han; Ping Liu; Xiao-Rong Liu; Lan-Yue Zhang (Natural Product Research, 2024)

Gas6-Axl signal promotes indoor VOCs exposure-induced pulmonary fibrosis via pulmonary microvascular endothelial cells–fibroblasts cross-talk - Qingping Liu; Yong Niu; Zijie Pei; Yizhe Yang; Yujia Xie; Mengruo Wang; Jingyuan Wang; Mengqi Wu; Jie Zheng; Peihao Yang; Haiyan Hao; Yaxian Pang; et al. (Journal of Hazardous Materials, 2024)

Mass cytometry revealed the circulating immune cell landscape across different Suzuki stages of Moyamoya disease - Chenglong Liu; Peicong Ge; Bojian Zhang; Liujia Chan; Yuheng Pang; Chuming Tao; Junsheng Li; Qiheng He; Wei Liu; Siqi Mou; Zhiyao Zheng; Zhikang Zhao; et al. (Immunologic Research, 2024)
Moyamoya disease (MMD) is a cerebrovascular disorder marked by progressive arterial narrowing, categorized into six stages known as Suzuki stages based on angiographic features. Growing evidence indicates a pivotal role of systemic immune and inflammatory responses in the initiation and advancement of MMD. This study employs high-dimensional mass cytometry to reveal the immunophenotypic characteristics of peripheral blood immune cells (PBMCs) at various Suzuki stages, offering insights into the progression of MMD. PBMC samples from eight patients with early-stage MMD (Suzuki stages II and III) and eight patients with later-stage MMD (Suzuki stages IV, V, and VI) were analyzed using high-dimensional mass cytometry to evaluate the frequency and phenotype of immune cell subtypes. We identified 15 cell clusters and found that the immunological features of early-stage MMD and later-stage MMD are composed of cluster variations. In this study, we confirmed that, compared to later-stage MMD, the early-stage MMD group exhibits an increase in non-classical monocytes. As the Suzuki stage level increases, the proportions of plasmacytoid DCs and monocyte-derived DCs decrease. Furthermore, T cells, monocytes, DCs, and PMN-MDSCs in the early-stage MMD group show activation of the canonical NF-κB signaling pathway. We summarized and compared the similarities and differences between early-stage MMD patients and later-stage MMD patients. There is a potential role of circulating immune dysfunction and inflammatory responses in the onset and development of MMD.

Characteristics and degradation mechanisms of polychlorinated naphthalenes in surface soil in Yangtze River Delta, China - Zherui Zhang; Guohua Zhu; Yahui Liu; Xin Zhou; Bingcheng Lin; Ziyuan Qi; Shanshan Zhang; Yueyao Yang; Xin Li; Rong Jin; Minghui Zheng (Chemosphere, 2024)

Interior decorative volatile organic compounds exposure induces sleep disorders through aberrant branched chain amino acid transaminase 2 mediated glutamatergic signaling resulting from a neuroinflammatory cascade - Jie Zheng; Mengqi Wu; Yaxian Pang; Qingping Liu; Yan Liu; Xiaoting Jin; Jinglong Tang; Lei Bao; Yujie Niu; Yuxin Zheng; Rong Zhang (Science of The Total Environment, 2024)

Ecological response to global changes in Lake Genco, a remote alpine lake on the Southeast Tibetan Plateau, over the past two centuries - Yanjie Zhao; Rong Wang; Hengshuai Qiu; Jianan Zheng; Kexin Zhu; Wenxiu Zheng; Xiangdong Yang; Enlou Zhang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Study on long-term surface settlement induced by shield tunneling in under-consolidated soft ground - Hai-Bo Wang; Rong-Jun Zhang; Feng-Juan Tao; Jun-Jie Zheng (Tunnelling and Underground Space Technology, 2024)

Chemical constituents of the deep-sea-derived fungus Trichoderma simmonsii ZEN3 and their chemotaxonomic significance - Li-Fang Liu; Yuan Wang; Rong Chao; Lin Xu; Zheng-Biao Zou; Kai Zhang; Ming-Min Xie; Xian-Qiang Chen; Cheng-Hai Gao; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Chemical constituents and chemotaxonomic research of the deep-sea-derived fungus Aspergillus japonicus W6 - Tong Yu; Rong Chao; Zheng-Biao Zou; Jia-Xin Duan; Kai Zhang; You Li; Ming-Min Xie; Yong Zhang; Ying-Ni Pan; Xian-Wen Yang (Biochemical Systematics and Ecology, 2024)

Draft Genome Sequence of Candida saopaulonensis from a Very Premature Infant with Sepsis - Ya-Ting Ning; Rong-Chen Dai; Zheng-Yu Luo; Meng Xiao; Yingchun Xu; Qun Yan; Li Zhang (Mycopathologia, 2024)
The rare fungus Candida saopaulonensis has never been reported to be associated with human infection. We report the draft genome sequence of the first clinical isolate of C. saopaulonensis, which was isolated from a very premature infant with sepsis. This is the first genome assembly reaching the near-complete chromosomal level with structural annotation for this species, opening up avenues for exploring evolutionary patterns and genetic mechanisms of pathogenesis.

Tracking diarrhea viruses and mpox virus using the wastewater surveillance network in Hong Kong - Xiawan Zheng; Keyue Zhao; Bingjie Xue; Yu Deng; Xiaoqing Xu; Weifu Yan; Chao Rong; Kathy Leung; Joseph T. Wu; Gabriel M. Leung; Malik Peiris; Leo L.M. Poon; et al. (Water Research, 2024)

Response of lake phytoplankton to climate oscillation on the northeastern Tibetan Plateau: Evidence from a 1400-year-old sedimentary archive - Hanxiao Zhang; Jianan Zheng; Rong Wang; Yong Liu; Yang Gao; Fengchang Wu; Shouliang Huo (Science Bulletin, 2024)

Straw management adopted by large farms sustains grain yield but mitigates greenhouse gas emissions - Zhenzhen Li; Yong Lin; Zheng-Rong Kan; Sana ur Rehman; Atta Mohi Ud Din; Feng-Min Li; Shixiang Zhang; Ping Wu; Yingfu Ding; Chensheng Xu; Congying Rao; Huaxin Dai; et al. (Field Crops Research, 2024)

NiCoP cocatalyst modified g-C3N4 as ohmic junction photocatalyst for efficient degradation of tetracycline under visible light - Qinyi Gu; Chujun Feng; Jian Rong; Yuzhe Zhang; Xudong Zheng; Jinfeng Mei; Zhongyu Li; Song Xu (Environmental Research, 2024)

Graphene oxide quantum dots (GOQDs) induce behavioral disorders via the disturbance of kynurenine pathway in zebrafish larvae - Shun Deng; Enming Zhang; Yunyang Zhao; Hao Guo; Lan Luo; Song Yi; Bingxin Zheng; Xiaoyuan Mu; Kezhu Yuan; Xuangen Deng; Haibo Rong; Yanbo Ma; et al. (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Using the paddy eco-ditch wetland system to reduce nitrogen non-point source pollution discharge from paddies: A consecutive six-year study in the Yunnan Plateau, China - Huanhao Han; Xinru Wang; Haili Zheng; Bo Liu; Rong Gao; Yuanlai Cui; Xiaogang Liu; Shixiang Gu; Bochao Zhang; Ming Yang (Agriculture, Ecosystems & Environment, 2024)

Bisphenol F exposure induces depression-like changes: Roles of the kynurenine metabolic pathway along the “liver-brain” axis - Zheng Yu; Yuxin Lin; Linlin Wu; Luyao Wang; Yichun Fan; Liuting Xu; Linwei Zhang; Weilan Wu; Jingxian Tao; Fei Huan; Wenwei Liu; Jun Wang; et al. (Environmental Pollution, 2024)

Iron-carbon micro-electrolysis facilitates autotrophic denitrification and Feammox in tidal flow constructed wetlands for enhanced nitrogen removal and reduced N2O emissions - Liping Zhao; Yucong Zheng; Zhenzhen Wang; Dongxian Zhang; Duo Ma; Yaqian Zhao; Xiaochang C. Wang; Rong Chen; Mawuli Dzakpasu (Chemical Engineering Journal, 2024)

In-situ GSH-responsive gas nanogenerator for active NIR-II FL/PA imaging and synergistic restoration the macrophage niche in rheumatoid arthritis - Xiaochun Zheng; Weiwei Kang; Yarong Jin; Xin Zhang; Wenxuan Wang; Dongsheng Li; Shutong Wu; Lin Chen; Shichao Meng; Rong Dai; Ziliang Zheng; Ruiping Zhang (Chemical Engineering Journal, 2024)

Polystyrene nanoplastics inhibit beige fat function and exacerbate metabolic disorder in high-fat diet-fed mice - Lina Zhang; Baocheng Wan; Jiangfei Zheng; Liwei Chen; Ye Xuan; Rong Zhang; Zhuo Chen; Cheng Hu; Yi Zhang; Chonghuai Yan (Science of The Total Environment, 2024)

Hub gene ELK3-mediated reprogramming lipid metabolism regulates phenotypic switching of pulmonary artery smooth muscle cells to develop pulmonary arterial hypertension induced by PM2.5 - Qingping Liu; Yizhe Yang; Mengqi Wu; Mengruo Wang; Peihao Yang; Jie Zheng; Zhe Du; Yaxian Pang; Lei Bao; Yujie Niu; Rong Zhang (Journal of Hazardous Materials, 2024)

Flexible and binder free electrode with d-p band center manipulated MoTe2 nanosheets towards high energy Lithium–Sulfur batteries - Meng Guo; Shaonan Gu; Rong Zhou; Zheng Zhang; Shuzheng Xu; Yinan Wang; Guowei Zhou (Chemical Engineering Journal, 2024)

A multi-species pest recognition and counting method based on a density map in the greenhouse - Zhiqin Zhang; Jiacheng Rong; Zhongxian Qi; Yan Yang; Xiajun Zheng; Jin Gao; Wei Li; Ting Yuan (Computers and Electronics in Agriculture, 2024)

Uranium speciation and distribution on the surface of Shewanella putrefaciens in the presence of inorganic phosphate and zero-valent iron under anaerobic conditions - Guo-Xiu Xuan; Guo-Hao Zhang; Wen-Cai Cheng; Chun-Yan Ma; Qing-Rong Li; En-Tong Liu; Wen-Ge He; Fa-Qin Dong; Xiao-An Li; Zheng-Guo Chen; Xiao-Qin Nie (Science of The Total Environment, 2024)

An implicit stabilized material point method for modelling coupled hydromechanical problems in two-phase geomaterials - Qin-yang Sang; Yong-lin Xiong; Rong-yue Zheng; Xiao-hua Bao; Guan-lin Ye; Sheng Zhang (Computers and Geotechnics, 2024)

Associations of legacy perfluoroalkyl and polyfluoroalkyl substances, alternatives, and isomers with gestational diabetes mellitus and glucose homeostasis among women conceiving through assisted reproduction in Shanghai, China - Dandan Mao; Guodong Ding; Zixia Wang; Jiuru Zhao; Hong Li; Xiaoning Lei; Jiaqi Zheng; Yan Zhang; Rong Shi; Tao Yuan; Zhiwei Liu; Yu Gao; et al. (Environmental Science and Pollution Research, 2024)

Systematic loss in biotic heterogeneity but not biodiversity across multiple trophic levels in Erhai lake, China - Wenxiu Zheng; Enlou Zhang; Peter Guy Langdon; Rong Wang (Science of The Total Environment, 2024)

The benefit of omeprazole exposure on all-cause mortality and length of ICU/hospital stay might vary with age in critically ill pediatric patients: A cohort study - Fang-Fang Jiang; Yu Guo; Zheng Zhang; Sun-Jun Yin; Yu-Xin Fan; Yan-Hua Huang; Ya-Jia Li; Li-Rong Chen; Kai Qian; Gong-Hao He (European Journal of Clinical Pharmacology, 2024)

Driving model of land use change on the evolution of carbon stock: a case study of Chongqing, China - Luoshan Zheng; Yangbing Li; Yan Chen; Rong Wang; Shijie Yan; Chunhua Xia; Bing Zhang; Jing’an Shao (Environmental Science and Pollution Research, 2023)

Mystery of bisphenol F-induced nonalcoholic fatty liver disease-like changes: Roles of Drp1-mediated abnormal mitochondrial fission in lipid droplet deposition - Linwei Zhang; Xuexue Xie; Jingxian Tao; Sizhe Wang; Miaoyang Hu; Xi Wang; Zheng Yu; Liuting Xu; Yuxin Lin; Weilan Wu; Jie Cheng; Linlin Wu; et al. (Science of The Total Environment, 2023)

Relative contribution of roots and symbiotic fungi to wheat nitrogen uptake and N2O emissions under straw burial - Zheng-Rong Kan; Yanling Li; Ruoyan Yang; Xinyu Yang; Qihang Wei; Ahmad Latif Virk; Jianying Qi; Feng-Min Li; Zichang Zhang; Haishui Yang (Rhizosphere, 2023)

Review: Phytate modification serves as a novel adsorption strategy for the removal of heavy metal pollution in aqueous environments - Xiaoliang Xue; Yuzhu Han; Xinming Wu; Hongji Wang; Shuang Wang; Jiaqi Zheng; Rong Ran; Chaowen Zhang (Journal of Environmental Chemical Engineering, 2023)

Synergistic modification of ultrasound and bamboo leaf flavonoid on the rheological properties, multi-scale structure, and in vitro digestibility of pea starch - Rong Hu; Liangru Wu; Xueqin Liao; Fusheng Zhang; Jiong Zheng (Food Chemistry, 2023)

Facile spinning of tough and conductive eutectogel fibers via Li+-induced dense hydrogen-bond networks - Lingtao Fang; Chi Zhang; Wenjiao Ge; Mingming Rong; Fan Chen; Zijian Chen; Xiaohui Wang; Zijian Zheng; Qiyao Huang (Chemical Engineering Journal, 2023)

Screening of small molecule compounds targeting hnRNPA2 protein - Yuan-Rong Zheng; Chao-Jie Wang; Ling Yang; Yu-Jun Zhang; Mei-Juan Fang; He Chang; Kai-Qiang Guo; Song-Lin Shi (Medicinal Chemistry Research, 2023)

Treg plasticity and human diseases - Zheng Zhang; Jihua Guo; Rong Jia (Inflammation Research, 2023)

Experimental infection and co-infection with Chinese strains of Ehrlichia canis and Babesia vogeli in intact and splenectomized dogs: Insights on clinical, hematologic and treatment responses - Jilei Zhang; Jiawei Wang; Patrick John Kelly; Yuanyuan Zhang; Min Li; Jing Li; Rong Zhang; Yaoyao Wang; Ke Huang; Jinfeng You; Haixiang Qiu; Xiaofeng Zheng; et al. (Veterinary Parasitology, 2023)

Efficacy of pterostilbene suppression on Aspergillus flavus growth, aflatoxin B1 biosynthesis and potential mechanisms - Yong-Mei Hu; Yi-Rong Wang; Wen-Bin Zhao; Yan Yan Ding; Zheng-Rong Wu; Guang-Han Wang; Peng Deng; Shao-Yong Zhang; Jun-Xia An; Zhi-Jun Zhang; Xiong-Fei Luo; Ying-Qian Liu (International Journal of Food Microbiology, 2023)

Complex coacervation of type II collagen with anionic polysaccharides: Effects of solution pH and molecular conformation of polysaccharide - Rong Xu; Lin Zheng; Sirui Zhang; Mingtao Huang; Mouming Zhao (Food Hydrocolloids, 2023)

Fine mapping and candidate gene analysis of a novel fertility restorer gene for C-type cytoplasmic male sterility in maize (Zea mays L.) - Peng Zhang; Zhuofan Zhao; Mingmin Zheng; Yongming Liu; Qunkai Niu; Xiaowei Liu; Ziwen Shi; Hongyang Yi; Tao Yu; Tingzhao Rong; Moju Cao (Theoretical and Applied Genetics, 2023)

High phytoplankton diversity in eutrophic states impedes lake recovery - Rong Wang; C. Patrick Doncaster; Wenxiu Zheng; Min Xu; Hui Yang; Yun Li; Yongjiu Cai; Yanjie Zhao; Enlou Zhang; Xiangdong Yang; Boqiang Qin (Journal of Biogeography, 2023)
Aim The widely observed positive response of productivity to biodiversity, known as the biodiversity‐productivity relationship (BPR), underpins nature‐based solutions for mitigating and adapting to global changes. Little is known of the role of such emergent processes in the restoration of damaged ecosystems. Here, we test for evidence of a BPR in degraded freshwater lakes, and its role in underpinning or undermining lake recovery from eutrophic states. Location Lower Yangtze and Huaihe river basins, China, East Asia. Taxa Freshwater phytoplankton; also macrophytes, fish, zooplankton and zoobenthos. Methods A systematic review of biodiversity studies was conducted to enumerate freshwater biodiversity change during eutrophication, encompassing 572 samples from 155 lakes in East China. Empirical samples were then taken of 93 phytoplankton communities from 38 lakes in ecologically degraded states of eutrophication. Samples were analysed for niche overlap in relation to biodiversity and productivity, and metrics of network structure indicative of community stability. Results Reviewed publications on eutrophication in East China lakes revealed losses in biodiversity of macrophytes, fishes, zooplankton and zoobenthos but not phytoplankton. Empirically sampled eutrophic lakes maintained high phytoplankton biodiversity through niche differentiation, and phytoplankton biodiversity correlated positively with biomass, in line with the expectations of BPR. Conclusions The positive effect of biodiversity on phytoplankton productivity in eutrophic lakes acts in opposition to the negative impacts on productivity induced by eutrophication‐management strategies of nutrient suppression. In degraded systems, the BPR contributes to sustaining productivity of lake phytoplankton communities, impeding recovery from a eutrophic state. This is a case of the BPR playing an undesirable role at the ecosystem level. Lake recovery programmes need to anticipate that the control of phytoplankton biomass will depend on reducing nutrients to a level sufficient to degrade the internal structure of the phytoplankton community.

Revealing the hidden burden for lake management: the sediment phosphorus storage pools in Eastern Plain Lake Zone, China - Chenxue Zhang; Yanjie Zhao; Min Xu; Wenxiu Zheng; Yu Zhao; Bo Qin; Rong Wang (Environmental Science and Pollution Research, 2023)

The impact of crop residue return on the food–carbon–water–energy nexus in a rice–wheat rotation system under climate warming - Li-Yao Zhou; Yong-he Zhu; Zheng-Rong Kan; Feng-Min Li; Feng Zhang (Science of The Total Environment, 2023)

Alignment of Fe3O4/CNT electrodes via magnetic blade printing for wireless stress-direction-recognizing strain sensor - Guangwei Wang; Chenhao Cong; Xianbing Zheng; Hongjiang Li; Fuhao Jiang; Xuhao Wang; Rong Li; Mingliang Jin; Pengfei Zhang; Junru Li; Chuanwei Zhang; SeHyun Kim; et al. (Chemical Engineering Journal, 2023)

The space-charge region at NiFe-MOF⊆LDH p-n junction by self-sacrificing LDH to boost oxygen evolution tandem with in-situ electro-Fenton - Na Zhang; Shi-Xian Guan; Qing Zhang; Jia-Rong Zhao; Jian-Yong Zhang; Qin-Fei Ke; Yong-Zheng Fang (Chemical Engineering Journal, 2023)

Transcriptomics reveals key regulatory pathways and genes associated with skin diseases induced by face paint usage - Bin Wang; Zhaohao Zheng; Ling Chen; Wenhui Zhang; Yujie He; Bing Wu; Rong Ji (Science of The Total Environment, 2023)

Characterization of elastoplastic behavior and retrieval of active zone depth for expansive soil slopes in the middle-route channel head of the South-to-North Water Diversion Project, China, using InSAR time series - Ziyuan Li; Jun Hu; Xing Zhang; Wanji Zheng; Wenqing Wu; Yaogang Chen; Pinjun Tang; Rong Gui (Remote Sensing of Environment, 2023)

Site-specific Atg13 methylation-mediated autophagy regulates epithelial inflammation in PM2.5-induced pulmonary fibrosis - Jie Ning; Zijie Pei; Mengruo Wang; Huaifang Hu; Meiyu Chen; Qingping Liu; Mengqi Wu; Peihao Yang; Zihan Geng; Jie Zheng; Zhe Du; Wentao Hu; et al. (Journal of Hazardous Materials, 2023)

Improved emulsified oil removal approach for industrial coal pyrolysis wastewater by flocculation under pressurized CO2 atmosphere - Bokun Chen; Caichun Zheng; Jicheng Bi; Xuan Qu; Rong Zhang; Xinbo Liu; Yanqi Yang (Journal of Cleaner Production, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Insights into the roles of humic acids in facilitating the anaerobic digestion process - Rong Zhu; Miao Yan; Yun Zhang; Hua Zou; Yi Zheng; Rongbo Guo; Shanfei Fu (Waste Management, 2023)

Corrigendum to “Graphene quantum dots (GQDs) induce thigmotactic effect in zebrafish larvae via modulating key genes and metabolites related to synaptic plasticity” [Toxicology 487 (2023) 1–13] - Shun Deng; Enming Zhang; Junyu Tao; Yunyang Zhao; Wenbo Huo; Hao Guo; Bingxin Zheng; Xiaoyuan Mu; Kezhu Yuan; Xuangen Deng; Hai Shen; Haibo Rong; et al. (Toxicology, 2023)

Detection of spatiotemporal changes in ecological quality in the Chinese mainland: Trends and attributes - Yang Li; Haifeng Tian; Jingfei Zhang; Siqi Lu; Zhixiang Xie; Wei Shen; Zhicheng Zheng; Mengdi Li; Peijun Rong; Yaochen Qin (Science of The Total Environment, 2023)

Synergistic degradation of tetracycline from Mo2C/MoOx films mediated peroxymonosulfate activation and visible-light triggered photocatalysis - Zheng Lian; Ting Wu; Xining Zhang; Shuangfei Cai; Youlin Xiong; Rong Yang (Chemical Engineering Journal, 2023)

CORM-3 alleviates the intestinal injury in a rodent model of hemorrhage shock and resuscitation: roles of GFAP-positive glia - Li-Min Zhang; Yue Xin; Rong-Xin Song; Wei-Chao Zheng; Jin-Shu Hu; Jie-Xia Wang; Zhi-You Wu; Dong-Xue Zhang (Journal of Molecular Histology, 2023)

RETRACTED: Using organo–mineral complex material to prevent the migration of soil Cd and As into crops: An agricultural practice and chemical mechanism study - Xuehao Zheng; Miaomiao Zhao; Lina Sun; Luge Rong; Bin Zhang; Fengjie Fan; Fangxi Zhang; Chengqiang Shu; Xiangyu Shi; Dan Zhao; Jianfeng Fu; Yuxin Zhang; et al. (Science of The Total Environment, 2023)

Achieving high yield and nitrogen agronomic efficiency by coupling wheat varieties with soil fertility - Keyu Ren; Minggang Xu; Rong Li; Lei Zheng; Huiying Wang; Shaogui Liu; Wenju Zhang; Yinghua Duan; Changai Lu (Science of The Total Environment, 2023)

Investigating the thermal conductivity and flame-retardant properties of BN/MoS2/PCNF composite film containing low BN and MoS2 nanosheets loading - Lei Yang; Wei Xu; Xiaolong Shi; Menglin Wu; Ziyi Yan; Qing Zheng; Gongneng Feng; Li Zhang; Rong Shao (Carbohydrate Polymers, 2023)

Characterization of dissolved organic matter content, composition, and source during spring algal bloom in tributaries of the Three Gorges Reservoir - Rong Xiang; Zebin Tian; Chuandong Zhang; Binghui Zheng; Haifeng Jia (Science of The Total Environment, 2023)

The city-wide full-scale interactive application of sewage surveillance programme for assisting real-time COVID-19 pandemic control – A case study in Hong Kong - Wai-yin Ng; Wai Thoe; Rong Yang; Wai-ping Cheung; Che-kong Chen; King-ho To; Kan-ming Pak; Hon-wan Leung; Wai-kwan Lai; Tsz-kin Wong; Tat-kwong Lau; Ka-wing Au; et al. (Science of The Total Environment, 2023)

Four anti-inflammatory aromadendrane sesquiterpenoid fucosides and other constituents from Pittosporum glabratum var. neriifolium - Bai-Tong Sha; Rong Huang; Qiang-Guo Zhang; Sheng-Nan Guan; Jia-Qi Ding; Xin-Zheng Liu; Xiu-Yun Zhang (Phytochemistry Letters, 2023)

The mechanisms of rapid seed germination in Caragana species adapted to low mean annual precipitation - Shi-Hua Qi; Guang-Qian Yao; Md. Mahadi Hasan; Hui Jiang; Xu-Dong Liu; Zheng-Fei Nie; Xia-Yi Zhang; Ya-Xian Du; Xue-Qian Tian; Feng-Ping Li; Xue-Rong Li; Xiang-Wen Fang (Trees, 2023)

Secukinumab plays a synergistic role with starvation therapy in promoting autophagic cell death of hepatocellular carcinoma via inhibiting IL-17A-increased BCL2 level - Rong Tang; Linmei Zheng; Jinfang Zheng; Jincai Wu; Pingping Chen; Jiacheng Chen; Dafeng Xu; Yongchao Zeng; Qijin Li; Zhensheng Zhang (In Vitro Cellular & Developmental Biology - Animal, 2023)

Responses of Bacillus sp. under Cu(II) stress in relation to extracellular polymeric substances and functional gene expression level - Ling-ling Wang; Zheng-yan Yin; Yun Xu; Miao-yu Deng; Kai-ming Zhang; Quan Wang; Rong-ping Chen; Lei Yu (Environmental Science and Pollution Research, 2023)

Flooding duration affects the temperature sensitivity of soil extracellular enzyme activities in a lakeshore wetland in Poyang Lake, China - Xingyun Huang; Kexin Wang; Xiuting Wen; Jie Liu; Yan Zhang; Jun Rong; Ming Nie; Chun Fu; Bofu Zheng; Zhifen Yuan; Leiqiang Gong; Huiying Zhan; et al. (Science of The Total Environment, 2023)

Exposure to real-ambient particulate matter induced vascular hypertrophy through activation of PDGFRβ - Hongxu Bao; Benying Li; Qing You; Xinyu Dun; Zhen Zhang; Yanan Liang; Yahui Li; Qixiao Jiang; Rong Zhang; Rui Chen; Wen Chen; Yuxin Zheng; et al. (Journal of Hazardous Materials, 2023)

Biochar enhanced organic matter transformation during pig manure composting: Roles of the cellulase activity and fungal community - Yanan Yin; Mengtong Li; Xiaohui Tao; Chao Yang; Wenrong Zhang; Haichao Li; Yucong Zheng; Xiaochang Wang; Rong Chen (Journal of Environmental Management, 2023)

Cenozoic clockwise rotation of the northeastern Tibetan Plateau: Paleomagnetic evidence from volcanic sequences in the West Qinling Mountain - Weitao Wang; Rong Huang; Ying Wu; Kang Liu; Zhuqi Zhang; Yipeng Zhang; Caicai Liu; Dewen Zheng; Peizhen Zhang (Global and Planetary Change, 2023)

An oligosaccharide marker for rapid authentication of edible bird’s nest - Li-Feng Li; Hui-Yuan Cheng; Jun Lang; Tin-Long Wong; Ji-Xia Zhang; Wen-Jie Wu; Quan-Wei Zhang; Hau-Yee Kong; Check-Hei Lai; Hau-Yee Fung; Man Liu; Wan-Rong Bao; et al. (Food Chemistry, 2023)

Degradation of polymeric polyproanthocyanidins from black chokeberry by microwave-assisted nucleophilic technique of sulfite/catechin: Reaction kinetics, antioxidation and structural analysis - Miao Li; Pu Li; Yufeng Xu; Baiqing Zhang; Jinfeng Li; Weitian Zhong; Hui Zang; Hui Zheng; Haifeng Rong; Fengming Ma (Food Chemistry, 2023)

Nonlinear gas-spring DVA for seismic response control: Experiment and numerical simulation - Kunjie Rong; Zheng Lu; Jiawei Zhang; Mengyao Zhou; Weiyuan Huang (Engineering Structures, 2023)

Considering flood scaling property in multi-objective calibration of the SWAT model: a case study in Zijinguan watershed, Northern China - Yanchen Zheng; Jianzhu Li; Ting Zhang; Youtong Rong; Ping Feng (Natural Hazards, 2023)

DNA damage and up-regulation of PARP-1 induced by columbin in vitro and in vivo - Yufen Liao; Xin Wang; Guangyun Ran; Shiyu Zhang; Chutian Wu; Rong Tan; Ying Liu; Yan He; Ting Liu; Zhongxiu Wu; Ying Peng; Weiwei Li; et al. (Toxicology Letters, 2023)

Real-ambient particulate matter exposure-induced FGFR1 methylation contributes to cardiac dysfunction via lipid metabolism disruption - Benying Li; Yanan Liang; Hongxu Bao; Daochuan Li; Ying Zhang; Xinyu Dun; Zijian Xu; Andong Ji; Zhen Zhang; Yahui Li; Rong Zhang; Wen Chen; et al. (Science of The Total Environment, 2023)

Formation of RNA adducts resulting from metabolic activation of spice ingredient safrole mediated by P450 enzymes and sulfotransferases - Xin Wang; Guangyun Ran; Yufen Liao; Bowen Gong; Chutian Wu; Rong Tan; Ying Liu; Shiyu Zhang; Ying Peng; Weiwei Li; Jiang Zheng (Food and Chemical Toxicology, 2023)

LncRNA CFAR promotes cardiac fibrosis via the miR-449a-5p/LOXL3/mTOR axis - Mingyu Zhang; Bowen Zhang; Xiaohan Wang; Jiahang Song; Ming Tong; Zheng Dong; Jiaonan Xu; Meng Liu; Yuan Jiang; Ning Wang; Ying Wang; Zhimin Du; et al. (Science China Life Sciences, 2023)

Genome-wide DNA methylation and transcription analysis reveal the potential epigenetic mechanism of heat stress response in the sea cucumber Apostichopus japonicus - Mengyang Chang; Jianlong Ge; Meijie Liao; Xiaojun Rong; Yingeng Wang; Bin Li; Xinrong Li; Jinjin Wang; Zheng Zhang; Yongxiang Yu; Chunyuan Wang (Frontiers in Marine Science, 2023)
DNA methylation is an important epigenetic modification that regulates many biological processes. The sea cucumber Apostichopus japonicus often suffers from heat stress that affects its growth and leads to significant economic losses. In this study, the mRNA expression patterns and DNA methylation characteristics in the body wall of A. japonicus under heat stress were analyzed by whole-genome bisulfite sequencing (WGBS) and transcriptome sequencing (RNA-seq). We found that CpG was the main DNA methylation type, and heat stress caused a significant increase in the overall methylation level and methylation rate, especially in the intergenic region of the A. japonicus genome. In total, 1,409 differentially expressed genes (DEGs) and 17,927 differentially methylated genes (DMGs) were obtained by RNA-seq and WGBS, respectively. Association analysis between DNA methylation and transcription identified 569 negatively correlated genes in both DMGs and DEGs, which indicated that DNA methylation affects on transcriptional regulation in response to heat stress. These negatively correlated genes were significantly enriched in pathways related to energy metabolism and immunoregulation, such as the thyroid hormone signaling pathway, renin secretion, notch signaling pathway and microRNAs in cancer. In addition, potential key genes, including heat shock protein ( hsp70 ), calcium-activated chloride channel regulator 1( clca1 ), and tenascin R ( tnr ), were obtained and their expression and methylation were preliminarily verified. The results provide a new perspective for epigenetic and transcriptomic studies of A. japonicus response to heat stress, and provide a reference for breeding sea cucumbers resistant to high temperatures.

Graphene quantum dots (GQDs) induce thigmotactic effect in zebrafish larvae via modulating key genes and metabolites related to synaptic plasticity - Shun Deng; Enming Zhang; Junyu Tao; Yunyang Zhao; Wenbo Huo; Hao Guo; Bingxin Zheng; Xiaoyuan Mu; Kezhu Yuan; Xuangen Deng; Hai Shen; Haibo Rong; et al. (Toxicology, 2023)

Microbiota-mediated reactivation of triclosan oxidative metabolites in colon tissues - Hongna Zhang; Katherine Z. Sanidad; Jianan Zhang; Guangqiang Wang; Rong Zhang; Chengchen Hu; Yongfeng Lin; Thomas D. Haggerty; Julie Parsonnet; Yuxin Zheng; Guodong Zhang; Zongwei Cai (Journal of Hazardous Materials, 2023)

Changes in cropland soil carbon through improved management practices in China: A meta-analysis - Bai-Jian Lin; Ruo-Chen Li; Mu-Yu Yang; Zheng-Rong Kan; Ahmad Latif Virk; Yves N′Dri Bohoussou; Xin Zhao; Yash Pal Dang; Hai-Lin Zhang (Journal of Environmental Management, 2023)

Differences in lipid accumulation and mobilization in the hepatopancreas and ovary of female mud crab (Scylla paramamosain, Estampador, 1949) during ovarian development - Baojia Chen; Jia Zheng; Cuiying Chen; Kun Wu; Fan Lin; Lijun Ning; Hua Rong; Chuan Chen; Fei Xiao; Haotian Zhang; Xiaobo Wen (Aquaculture, 2023)

Ancient DNA reveals potentially toxic cyanobacteria increasing with climate change - Jifeng Zhang; Kun Shi; Hans W. Paerl; Kathleen M. Rühland; Yanli Yuan; Rong Wang; Jie Chen; Mengjuan Ge; Lingling Zheng; Zhiping Zhang; Boqiang Qin; Jianbao Liu; et al. (Water Research, 2023)

Ex vivo coronary endothelial cell activation associated with indoor coal combustion initiated atherosclerosis - Wanjun Zhang; Yaxian Pang; Wenting Cheng; Tao Wang; Yanting Li; Xin Li; Jianzhong Zhang; Xiaowen Xia; Yuxin Zheng; Rong Zhang; Jinglong Tang (Science of The Total Environment, 2023)

A 2D mesoporous hydrazone covalent organic framework for selective detection and ultrafast recovery of Au(III) from electronic waste - Li Zhang; Jia-Qi Fan; Qiong-Qing Zheng; Sai-Jin Xiao; Cheng-Rong Zhang; Shun-Mo Yi; Xin Liu; Wei Jiang; Quan-Gen Tan; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2023)

Selective separation of volatile fatty acids, nitrogen and phosphorus from anaerobic acidogenic fermentation via forward osmosis membrane process - Xian-Zheng Zhu; Long-Fei Wang; Xin-Rong Pan; Feng Zhang; Min-Sheng Huang; Wen-Wei Li; Hou-Qi Liu (Chemical Engineering Journal, 2023)

Enhanced phytoremediation of atrazine-contaminated soil by vetiver (Chrysopogon zizanioides L.) and associated bacteria - Faming Zhang; Shixian Sun; Yuhong Rong; Lili Mao; Shuchun Yang; Ling Qian; Rongbiao Li; Yi Zheng (Environmental Science and Pollution Research, 2023)

A study on the correlation between intrauterine microbiota and uterine pyogenesis in dogs - Hui-Hua Zheng; Chong-Tao Du; Yu-Zhu Zhang; Chao Yu; Rong-Lei Huang; Xin-Yue Tang; Guang-Hong Xie (Theriogenology, 2023)

Efficient synthesis of PdIr nanocatalysts with controllable surface composition for electrochemical oxidation of methanol - Ce Fu; Pan Wang; Rong-Hua Zhang; Luo-Yi Yan; Zheng Cheng; Xin Zhang; Xin-Wen Zhou (Fuel, 2023)

Programmable phthalocyanine-iron-based nanoreactor for fluorescence/magnetic resonance dual-modality imaging-guided sono/chemodynamic therapies - Dong Li; Jie Pan; Shuyu Xu; Bingwei Cheng; Shuaiying Wu; Qixuan Dai; Mei-Rong Ke; Bi-Yuan Zheng; Chengchao Chu; Chao Liu; Yang Zhang; Xiao Xu; et al. (Chemical Engineering Journal, 2023)

Comparative Toxicity of 3–5 Ringed Polycyclic Aromatic Hydrocarbons to Skeletal Development in Zebrafish Embryos and the Possible Reason - Ke Xu; Ying Zhang; Jingyan Zheng; Chonggang Wang; Rong Chen (Bulletin of Environmental Contamination and Toxicology, 2023)

Extracellular Mitochondria Activate Microglia and Contribute to Neuroinflammation in Traumatic Brain Injury - Chaonan Zhang; Chuan Liu; Fanjian Li; Mutian Zheng; Yafan Liu; Lei Li; Huaijin Yang; Shu Zhang; Chongjin Wang; Hongtao Rong; Hui Guo; Ying Li; et al. (Neurotoxicity Research, 2022)

Prediction model for disc cutter wear during hard rock breaking based on plastic removal abrasiveness mechanism - Lei She; She-rong Zhang; Chao Wang; Zheng-qiao Wu; Lun-chuang Yu; Li-xin Wang (Bulletin of Engineering Geology and the Environment, 2022)

Physiology, metabolism, antibiotic resistance, and genetic diversity of Harveyi clade bacteria isolated from coastal mariculture system in China in the last two decades - Hao Kang; Yongxiang Yu; Meijie Liao; Yingeng Wang; Guanpin Yang; Zheng Zhang; Bin Li; Xiaojun Rong; Chunyuan Wang (Frontiers in Marine Science, 2022)
Vibrio bacteria, particularly members of the Harveyi clade, are the most important pathogens of aquatic organisms that cause significant economic losses in the world. It is difficult to provide specific data on taxa of the Harveyi clade for biological research and prevention strategies. Therefore, we conducted an extensive phenotypic and antibiotic resistance study, as well as phylogenetic and molecular typing of 192 isolates of the Harveyi clade collection from 2000 to 2020 with a typical interannual difference from a coastal area in China. The isolates had a significant interspecific genetic and antibiotic resistance diversity. Based on the multilocus sequence analysis (MLSA) of housekeeping genes ( gyrB , pyrH , recA , and atpA ), 192 Harveyi clade isolates were rapidly and accurately classified into 10 species. The population of these isolates was composed of 95 sequence types (STs), of which 92 STs were newly identified, indicating a high degree of genetic diversity. ST327 ranked first, accounting for 11.5% of the total number of isolates (22 out of 192), followed by ST215 with 6.25%, while 63 STs included single isolates. At the metabolic level, the physiological and biochemical experiments revealed that all the Harveyi clade isolates were positive for oxidase and negative for melibiose. The isolates showed a varied tolerance to 11 antibiotics. No isolates were resistant to neomycin. The percentages of sulfadimidine-resistant strains (61 out of 192), sulfadiazine (44 out of 192), sulfamonomethoxine (44 out of 192), sulfamethoxazole (33 out of 192), thiamphenicol (34 out of 192), ciprofloxacin (52 out of 192), and enrofloxacin (31 out of 192) were 31.77%, 22.92%, 22.92%, 17.19%, 17.71%, 27.08%, and 16.15%, respectively. A proportion of 61.8% of the isolates presented a multiple antibiotic resistance index (MARI) lower than 0.1, indicating that the risk of antibiotic resistance transmission of most of the Harveyi clade is low in mariculture systems in China. These results provide substantial data to support further studies on the identification and genetic and metabolic diversity of Harveyi clade isolates in mariculture systems in China.

Antifungal and insecticidal activities of rhein derivatives: synthesis, characterization and preliminary structure–activity relationship studies - Xiang Zhu; Shunshun Chen; Yan Zheng; Yong Zhang; Tom Hsiang; Rong Huang; Jingwei Qi; Tian Gan; Yue Chang; Junkai Li (Natural Product Research, 2022)

Correction to: Higher sequestration of wheat versus maize crop carbon in soil under rotations - Zheng-Rong Kan; Shou-Wei Han; Wen-Xuan Liu; Xin Zhao; Rattan Lal; Hai-Lin Zhang (Environmental Chemistry Letters, 2022)

Analysis of the atmospheric direct dynamic source for the westerly extended WPSH and record-breaking Plum Rain in 2020 - Yuheng Zhao; Jianbo Cheng; Guolin Feng; Rong Zhi; Zhihai Zheng; Zengping Zhang (Climate Dynamics, 2022)

Heterologous expression of ZmNF-YA12 confers tolerance to drought and salt stress in Arabidopsis - Tongtong Zhang; Dengyu Zheng; Chun Zhang; Zhongyi Wu; Rong Yu; Zhongbao Zhang (Plant Biotechnology Reports, 2022)

Antimicrobial Resistance and Genotype Characteristics of Vibrio scophthalmi Isolated from Diseased Mariculture Fish Intestines With Typical Inter-Annual Variability - Yongxiang Yu; Xiao Liu; Yingeng Wang; Meijie Liao; Miaomiao Tang; Xiaojun Rong; Chunyuan Wang; Bin Li; Zheng Zhang (Frontiers in Marine Science, 2022)
As an intestinal organism settled long-term within the gut of marine fish, Vibrio scophthalmi is a potential object for the bacterium genetic variation and adaptation research. The genetic diversity, antimicrobial resistance phenotype, and genotype of 33 V. scophthalmi isolated from diseased marine fish intestines between 2002 and 2020 were evaluated. The results showed that all isolates were frequently resistant to penicillins, cephalosporins, aminoglycosides, and macrolides and displayed multidrug-resistant (MDR) phenotype in vitro . Thirty percent of isolates were resistant to more than 20 different drugs. The average insensitive (resistant and intermediate) rate of V. scophthalmi isolates was 49.5%~81.8% between 2002 and 2020, but the t-test revealed that there was no significant difference in the drug-resistance rate of V. scophthalmi isolates with typical interannual variability. Eleven antimicrobial resistance genes ( strB , strA , ant(3 ˝)-I , mphA , blaPSE , qnrS , tetC , tetE , tetM , tetS , and int1 ) were detected in these isolates, but the antimicrobial resistance phenotypes and genotypes of these isolates were not consistent. Enterobacterial repetitive intergenic consensus polymerase chain reaction (ERIC-PCR) analysis indicated that 33 isolates could be divided into two clusters (G1 and G3) and two single isolates (G2 and G4), and the G2 cluster was isolated from South Sea C. undulates with typical geographical species differences. There was no significant correlation between the drug susceptibility and the genetic types of V. scophthalmi isolates. The results reveal the mismatch phenomenon between antimicrobial resistance and genotype of inherent V. scophthalmi in the marine fish intestines, and the antimicrobial susceptibility isolates might be a potential risk source for storage and transmission of resistance genes.

Bmal1- and Per2-mediated regulation of the osteogenic differentiation and proliferation of mouse bone marrow mesenchymal stem cells by modulating the Wnt/β-catenin pathway - Jiawen Zheng; Lanxin Zhang; Zhen Tan; Qing Zhao; Xiaoyu Wei; Yuqing Yang; Rong Li (Molecular Biology Reports, 2022)

A low-cost in-situ CO2 sensor based on a membrane and NDIR for long-term measurement in seawater - Meng Li; Baolu Du; Jinjia Guo; Zhihao Zhang; Zeyu Lu; Rong’er Zheng (Journal of Oceanology and Limnology, 2022)

Correction to: Occurrence of Pestalotiopsis lushanensis causing leaf blight on Buddhist pine in China - Xiang-rong Zheng; Mao-jiao Zhang; Feng-mao Chen (European Journal of Plant Pathology, 2022)

Novel blood-based hypomethylation of SH3BP5 is associated with very early-stage lung adenocarcinoma - Rong Qiao; Runbo Zhong; Chunlan Liu; Feifei Di; Zheng Zhang; Ling Wang; Tian Xu; Yue Wang; Liping Dai; Wanjian Gu; Baohui Han; Rongxi Yang (Genes & Genomics, 2022)

Reasonable application range of flocculation–solidification combined method in treatment of hydraulically dredged mud slurry - Rong-Jun Zhang; Zhi-Hao Xu; Jun-Jie Zheng; Lin-Wei Tu; Zhan-fang Huang (Marine Georesources & Geotechnology, 2022)

Occurrence of Pestalotiopsis lushanensis causing leaf blight on Buddhist pine in China - Xiang-rong Zheng; Mao-jiao Zhang; Feng-mao Chen (European Journal of Plant Pathology, 2022)

Understanding the key factors determining rural domestic waste treatment behavior in China: a meta-analysis - Donghui Zheng; Jing Shen; Rong Li; Bei Jian; Jihong Zeng; Yongliang Mao; Xiaoning Zhang; Pradipta Halder; Mei Qu (Environmental Science and Pollution Research, 2022)

Higher sequestration of wheat versus maize crop carbon in soils under rotations - Zheng-Rong Kan; Shou-Wei Han; Wen-Xuan Liu; Xin Zhao; Rattan Lal; Hai-Lin Zhang (Environmental Chemistry Letters, 2022)

Human impacts alter driver–response relationships in lakes of Southwest China - Wenxiu Zheng; Enlou Zhang; Rong Wang; Peter Guy Langdon (Limnology and Oceanography, 2022)
Biodiversity and ecological stability are closely linked, and over recent timescales, anthropogenic impacts have accelerated losses in both from local to global scales. We attempt to show the combined response of diversity and stability of an aquatic community to changes in human activity as a driver. To address this, we measured the diversity and variability of chironomids and their drivers and nature of response to external conditions over the last century, based on 4 lake sediment sequences from Southwest China, one of world's 36 biodiversity hotspots. Our results showed that the driver–response relationship was linear in a lake without direct human impacts but nonlinear in human directly impacted lakes. Recent decreases in alpha diversity and increases in beta diversity were commonly recorded in all four lakes, suggesting that both species loss and a faster replacement of chironomid taxa are a regional phenomenon. However, in the same context of human‐induced global warming, increased variability and regime shifts only occurred in lowland lakes, directly disturbed by humans, highlighting that direct human impacts have overcome natural forcing as the determinant driver shaping the chironomid composition in these sites. In addition, we found that increases in beta diversity occurred prior to a regime shift and its character depends on how the community responds to the key external pressure. Our findings reveal that direct human disturbances have largely reshaped the chironomid composition and induced an earlier regime shift at the cost of species loss, resilience loss, and a change in driver–response type.

Mechanisms of soil organic carbon stability and its response to no‐till: A global synthesis and perspective - Zheng‐Rong Kan; Wen‐Xuan Liu; Wen‐Sheng Liu; Rattan Lal; Yash Pal Dang; Xin Zhao; Hai‐Lin Zhang (Global Change Biology, 2022)
Mechanisms of soil organic carbon (SOC) stabilization have been widely studied due to their relevance in the global carbon cycle. No‐till (NT) has been frequently adopted to sequester SOC; however, limited information is available regarding whether sequestered SOC will be stabilized for long term. Thus, we reviewed the mechanisms affecting SOC stability in NT systems, including the priming effects (PE), molecular structure of SOC, aggregate protection, association with soil minerals, microbial properties, and environmental effects. Although a more steady‐state molecular structure of SOC is observed in NT compared with conventional tillage (CT), SOC stability may depend more on physical and chemical protection. On average, NT improves macro‐aggregation by 32.7%, and lowers SOC mineralization in macro‐aggregates compared with CT. Chemical protection is also important due to the direct adsorption of organic molecules and the enhancement of aggregation by soil minerals. Higher microbial activity in NT could also produce binding agents to promote aggregation and the formation of metal‐oxidant organic complexes. Thus, microbial residues could be stabilized in soils over the long term through their attachment to mineral surfaces and entrapment of aggregates under NT. On average, NT reduces SOC mineralization by 18.8% and PE intensities after fresh carbon inputs by 21.0% compared with CT ( p Q 10 ) is observed in NT due to greater Q 10 in macro‐aggregates, an increase of soil moisture regime in NT could potentially constrain the improvement of Q 10 . This review improves process‐based understanding of the physical and chemical mechanism of protection that can act, independently or interactively, to enhance SOC preservation. It is concluded that SOC sequestered in NT systems is likely to be stabilized over the long term.

Predictive value of monocyte to HDL cholesterol ratio for stroke-associated pneumonia in patients with acute ischemic stroke - Yaming Sun; Juan Lu; Danni Zheng; Jufen Qian; Hongxin Zhang; Dong Xing; Fengdan Rong; Yongjun Cao; Chun-Feng Liu; Shoujiang You (Acta Neurologica Belgica, 2021)

The effect of the PARK16 rs11240572 variant on brain structure in Parkinson's disease - Lu-yan Gu; Shao-bing Dai; Cheng Zhou; Ting Gao; Jing-jing Wu; Yi Fang; Xiao-jun Guan; Tao Guo; Ran Zheng; Chongyao Jin; Xiao-jun Xu; Zhe Song; et al. (Brain Structure and Function, 2021)

Biomechanical Strengthening Design for Limb Articulation Based on Reconstructed Skeleton Kinesthetics - Jing-Hua Xu; Zheng-Xin Tu; Jing-Xuan Xu; Shu-You Zhang; Jian-Rong Tan (Journal of Medical and Biological Engineering, 2021)

Colonization Characteristics of Poplar Fungal Disease Biocontrol Bacteria N6-34 and the Inhibitory Effect on Pathogenic Fungi by Real-Time Fluorescence Quantitative PCR Detection - Rong-bo Sa; Jun-li Zhang; Ji-zheng Sun; Yan-xia Gao (Current Microbiology, 2021)

Surfactant-assisted adsorption of uranyl ions in aqueous solution on TiO2/polythiophene nanocomposite - Youqun Wang; Yinghui Xie; Zhiyang Zheng; Dejun Zeng; Ying Dai; Zhibin Zhang; Xiaohong Cao; Rong Zou; Yunhai Liu (Environmental Science and Pollution Research, 2021)

Transcutaneous Auricular Vagus Nerve Stimulation: From Concept to Application - Yu Wang; Shao-Yuan Li; Dan Wang; Mo-Zheng Wu; Jia-Kai He; Jin-Ling Zhang; Bin Zhao; Li-Wei Hou; Jun-Ying Wang; Lei Wang; Yi-Fei Wang; Yue Zhang; et al. (Neuroscience Bulletin, 2021)

Effects of Diversified Cropping Sequences and Tillage Practices on Soil Organic Carbon, Nitrogen, and Associated Fractions in the North China Plain - Ahmad Latif Virk; Wen-Sheng Liu; Jia-Rui Niu; Cheng-Tang Xu; Qiu-Yue Liu; Zheng-Rong Kan; Xin Zhao; Hai-Lin Zhang (Journal of Soil Science and Plant Nutrition, 2021)

Marinobacter shengliensis subsp. alexandrii Subsp. Nov., Isolated from Cultivable Phycosphere Microbiota of Highly Toxic Dinoflagellate Alexandrium catenella LZT09 and Description of Marinobacter shengliensis Subsp. shengliensis Subsp. Nov - Xi Yang; Rong Xiang; Nurhezreen Md Iqbal; Yu-Han Duan; Xiao-Ai Zhang; Lei Wang; Lin-Zeng Yu; Jia-Zhou Li; Ming-Fei Sun; Qiao Yang; Chun-Tian Zheng; Shen-Quan Liao (Current Microbiology, 2021)

Development of a Microfluidics-Based Quantitative Real-Time PCR to Rapidly Identify Photobacterium damselae subsp. damselae with Different Pathogenicity by Detecting the Presence of mcp or dly Gene - Zheng Zhang; Yongxiang Yu; Jing Chen; Yingeng Wang; Yong Jiang; Meijie Liao; Xiaojun Rong; Hao Zhang (Journal of Ocean University of China, 2021)

The intestine of artificially bred larval turbot (Scophthalmus maximus) contains a stable core group of microbiota - Zheng Zhang; Yongxiang Yu; Yan Jiang; Yingeng Wang; Meijie Liao; Xiaojun Rong; Qian Liu (Archives of Microbiology, 2020)

Soil bio-cementation using an improved 2-step injection method - Ming-Juan Cui; Jun-Jie Zheng; Rong-Jun Zhang; Han-Jiang Lai (Arabian Journal of Geosciences, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Effective identification of CRISPR/Cas9-induced and naturally occurred mutations in rice using a multiplex ligation-dependent probe amplification-based method - Sukumar Biswas; Rong Li; Jun Hong; Xiangxiang Zhao; Zheng Yuan; Dabing Zhang; Jianxin Shi (Theoretical and Applied Genetics, 2020)

Comparative transcriptome analysis reveals a gene expression profile that contributes to rhizome swelling in Panax japonicus var. major - Jun Rong Tang; Ying Chun Lu; Zheng Jie Gao; Wan Ling Song; Kun Hua Wei; Yan Zhao; Qing Yan Tang; Xue Jiao Li; Jun Wen Chen; Guang Hui Zhang; Guang Qiang Long; Wei Fan; et al. (Plant Biosystems, 2020)

Simulation of the landform change process on a purple soil slope due to tillage erosion and water erosion using UAV technology - Chao Yang; Zheng-an Su; Jian-rong Fan; Hai-dong Fang; Liang-tao Shi; Jian-hui Zhang; Zhou-yao He; Tao Zhou; Xiao-yi Wang (Journal of Mountain Science, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

MiR-145 alleviates Hcy-induced VSMC proliferation, migration, and phenotypic switch through repression of the PI3K/Akt/mTOR pathway - Minghao Zhang; Fan Li; Xiuyu Wang; Jian Gong; Yushan Xian; Guan Wang; Zihan Zheng; Chenxu Shang; Bo Wang; Yanhao He; Weirong Wang; Rong Lin (Histochemistry and Cell Biology, 2020)

Photoprotection capacity of microalgae improved by regulating the antenna size of light-harvesting complexes - Guang-Rong Hu; Yong Fan; Yan-Lin Zheng; Feng Xu; Lei Zhang; Fu-Li Li (Journal of Applied Phycology, 2020)

Comparative profiling of roots small RNA expression and corresponding gene ontology and pathway analyses for low- and high-cadmium–accumulating genotypes of wheat in response to cadmium stress - Min Zhou; Shigang Zheng; Yunfang Li; Rong Liu; Lei Zhang; Yu Wu (Functional & Integrative Genomics, 2020)

Steroidogenic acute regulatory protein/aldosterone synthase mediates angiotensin II-induced cardiac fibrosis and hypertrophy - Wei-Wei Zhang; Rong-Hua Zheng; Feng Bai; Katelyn Sturdivant; Ning-Ping Wang; Erskine A. James; Himangshu S. Bose; Zhi-Qing Zhao (Molecular Biology Reports, 2020)

Developing stripe rust resistant wheat (Triticum aestivum L.) lines with gene pyramiding strategy and marker-assisted selection - Rong Liu; Jing Lu; Min Zhou; Shigang Zheng; Zehou Liu; Chihong Zhang; Mei Du; Minxiu Wang; Yunfang Li; Yu Wu; Lei Zhang (Genetic Resources and Crop Evolution, 2020)

Characterization and diagnostic marker development for Yr28-rga1 conferring stripe rust resistance in wheat - Shigang Zheng; Yu Wu; Min Zhou; Lian Zeng; Rong Liu; Yunfang Li; Zehou Liu; Chihong Zhang; Lu Lu; Lei Zhang (European Journal of Plant Pathology, 2020)

Effects of Different Preservation Methods on Physicochemical Property of Marine Pathogen Vibrio anguillarum - Yongxiang Yu; Zheng Zhang; Yingeng Wang; Meijie Liao; Xiaojun Rong; Bin Li; Hao Zhang (Journal of Ocean University of China, 2019)

Combined gastroscopic and choledochoscopic transabdominal nasobiliary drainage - Song-mei Lou; Min Zhang; Zheng-rong Wu; Gui-xing Jiang; Hua Shen; Yi Dai; Yue-long Liang; Li-ping Cao; Guo-ping Ding (Journal of Zhejiang University-SCIENCE B, 2019)

Enhancing the mechanical properties of marine clay using cement solidification - Bhim Kumar Dahal; Jun-Jie Zheng; Rong-Jun Zhang; Ding-Bao Song (Marine Georesources & Geotechnology, 2019)

Influences of immersion bathing in Bacillus velezensis DY-6 on growth performance, non-specific immune enzyme activities and gut microbiota of Apostichopus japonicus - Jinyan Wang; Bin Li; Yingeng Wang; Meijie Liao; Xiaojun Rong; Zheng Zhang (Journal of Oceanology and Limnology, 2019)

First report of lettuce big-vein associated varicosavirus infecting lettuce in China - Guo-Hua Zheng; Ting Ye; Fu-Rong Liao; Wen-Zhu Zhang; Yan-Lin Ming (Journal of Plant Pathology, 2019)

First report of isolation and complete genome of Vibrio rotiferianus strain SSVR1601 from cage‐cultured black rockfish ( Sebastes schlegelii ) associated with skin ulcer - Zheng Zhang; Yong‐xiang Yu; Yong Jiang; Yin‐geng Wang; Mei‐jie Liao; Xiao‐jun Rong; Kai Wang; Hao Zhang; Jing Chen (Journal of Fish Diseases, 2019)
Vibrio rotiferianus is an important marine pathogen of various aquatic organisms and can be found widely distributed in the marine environment. To further characterize this pathogen, the pathogenic properties and genome of V. rotiferianus SSVR1601 isolated from Sebastes schlegelii with skin ulcer were analysed. SSVR1601 was shown to be short rod‐shaped cell with a single polar flagellum. Different degrees of pathological changes in fish kidney, intestine, gills and liver were observed after SSVR1601 challenge. The SSVR1601 genome consists of two chromosomes and two plasmids with a total of 5,717,113 bp, 42.04%–44.93% GC content, 5,269 predicted CDSs, 134 tRNAs and 40 rRNAs. The common virulence factors including OMPs, haemolysin, flagellin, DNase, entF , algU , tcpI , acfB and rfaD were found in strain SSVR1601. Furthermore, factors responsible for iron uptake ( fur , fepC and ccmC ) and types II, IV and VI secretion systems were detected, which are likely responsible for the pathogenicity of SSVR1601. The antimicrobial resistance genes, bacA , tet34 and norM, were detected based on Antibiotic Resistance Genes Database. The phylogenetic analysis revealed SSVR1601 to be most closely related to V. rotiferianus strains CAIM577 and B64D1.

Chronic stress impairs the aquaporin-4-mediated glymphatic transport through glucocorticoid signaling - Fang Wei; Jian Song; Cui Zhang; Jun Lin; Rong Xue; Li-Dong Shan; Shan Gong; Guo-Xing Zhang; Zheng-Hong Qin; Guang-Yin Xu; Lin-Hui Wang (Psychopharmacology, 2019)

Development of methods for effective identification of CRISPR/Cas9-induced indels in rice - Sukumar Biswas; Rong Li; Zheng Yuan; Dabing Zhang; Xiangxiang Zhao; Jianxin Shi (Plant Cell Reports, 2019)

Comparative analysis of root transcriptome profiles between low- and high-cadmium-accumulating genotypes of wheat in response to cadmium stress - Min Zhou; Shigang Zheng; Rong Liu; Jing Lu; Lu Lu; Chihong Zhang; Zehou Liu; Congpei Luo; Lei Zhang; Yu Wu (Functional & Integrative Genomics, 2019)

Relationship between polymorphisms of the lipid metabolism-related gene PLA2G16 and risk of colorectal cancer in the Chinese population - Xiao-Nv Xie; Jing Yu; Li-Hua Zhang; Zhi-Ying Luo; Dong-Sheng Ouyang; Ling-Jie Zheng; Chun-Yang Wang; Li Yang; Ling Chen; Zhi-Rong Tan (Functional & Integrative Genomics, 2019)

The Influence of Cellulosic Polymer’s Variables on Dissolution/Solubility of Amorphous Felodipine and Crystallization Inhibition from a Supersaturated State - Nian-Qiu Shi; Ying Jin; Yong Zhang; Xiao-Xia Che; Xiao Xiao; Gui-Hua Cui; Yu-Zhou Chen; Bo Feng; Zheng-Qiang Li; Xian-Rong Qi (AAPS PharmSciTech, 2019)

Thermo-elastoplastic Model for Soft Rock Considering Effects of Structure and Overconsolidation - Yong-lin Xiong; Qi-lai Yang; Sheng Zhang; Guan-lin Ye; Gan-bin Liu; Rong-yue Zheng; Feng Zhang (Rock Mechanics and Rock Engineering, 2018)

Endogenous Hydrogen Sulfide Promotes Apoptosis via Mitochondrial Pathways in the Livers of Broilers with Selenium Deficiency Exudative Diathesis Disease - Shu-fang Zheng; Rong-kun Bao; Qiao-jian Zhang; Sheng-chen Wang; Hong-jin Lin (Biological Trace Element Research, 2018)

Synthesis, antitumor evaluation and molecular docking study of a novel podophyllotoxin-lonidamine hybrid - Lei Zhang; Jie Zheng; Ying Rong; Chengli Yang; Li Long; Yingshu Xu; Yongzheng Chen; Jing Wang; Qizheng Yao (Medicinal Chemistry Research, 2018)

Neuroinflammation in acute hepatic encephalopathy rats: imaging and therapeutic effectiveness evaluation using 11C-PK11195 and 18F-DPA-714 micro-positron emission tomography - Song Luo; Xiang Kong; Jin Rong Wu; Chun Yan Wang; Ying Tian; Gang Zheng; Yun Yan Su; Guang Ming Lu; Long Jiang Zhang; Gui Fen Yang (Metabolic Brain Disease, 2018)

Comparison of gene co-networks reveals the molecular mechanisms of the rice (Oryza sativa L.) response to Rhizoctonia solani AG1 IA infection - Jinfeng Zhang; Wenjuan Zhao; Rong Fu; Chenglin Fu; Lingxia Wang; Huainian Liu; Shuangcheng Li; Qiming Deng; Shiquan Wang; Jun Zhu; Yueyang Liang; Ping Li; et al. (Functional & Integrative Genomics, 2018)

Diversity of herbaceous plants and bacterial communities regulates soil resistome across forest biomes - Hang‐Wei Hu; Jun‐Tao Wang; Brajesh K. Singh; Yu‐Rong Liu; Yong‐Liang Chen; Yu‐Jing Zhang; Ji‐Zheng He (Environmental Microbiology, 2018)
Summary Antibiotic resistance is ancient and prevalent in natural ecosystems and evolved long before the utilization of synthetic antibiotics started, but factors influencing the large‐scale distribution patterns of natural antibiotic resistance genes (ARGs) remain largely unknown. Here, a large‐scale investigation over 4000 km was performed to profile soil ARGs, plant communities and bacterial communities from 300 quadrats across five forest biomes with minimal human impact. We detected diverse and abundant ARGs in forests, including over 160 genes conferring resistance to eight major categories of antibiotics. The diversity of ARGs was strongly and positively correlated with the diversity of bacteria, herbaceous plants and mobile genetic elements (MGEs). The ARG composition was strongly correlated with the taxonomic structure of bacteria and herbs. Consistent with this strong correlation, structural equation modelling demonstrated that the positive effects of bacterial and herb communities on ARG patterns were maintained even when simultaneously accounting for multiple drivers (climate, spatial predictors and edaphic factors). These findings suggest a paradigm that the interactions between aboveground and belowground communities shape the large‐scale distribution of soil resistomes, providing new knowledge for tackling the emerging environmental antibiotic resistance.

Srk1 kinase, a SR protein‐specific kinase, is important for sexual reproduction, plant infection and pre‐mRNA processing in Fusarium graminearum - Guanghui Wang; Peng Sun; Ziwen Gong; Lianfeng Gu; Yi Lou; Wenqin Fang; Lianhu Zhang; Li Su; Tao Yang; Baohua Wang; Jie Zhou; Jin‐Rong Xu; et al. (Environmental Microbiology, 2018)
Summary SR protein‐specific kinases (SRPKs) uniquely with a spacer region are important splicing factors from yeast to human. However, little is known about their biological functions in filamentous fungi. Therefore, we characterized a SRPK called SRK1 in wheat scab fungus Fusarium graminearum . Our data showed that Srk1 is required for vegetative growth, sexual reproduction and plant infection, and plays critical roles in pre‐mRNA alternative splicing and gene expression. Remarkably, we found that Srk1 displayed dynamic shuttling between cytoplasm and the nucleus, which is regulated by the divergent spacer domain rather than its kinase activity, suggesting a regulatory mechanism for Srk1. Interestingly, Srk1‐GFP also localized to the septal pores, indicating a possible role of Srk1 unrelated to mRNA processing. Although both K1 and K2 lobes of the kinase domain are essential for Srk1 functions, the K2 but not K1 lobe is responsible for the septal pore localization. Lastly, we established that Srk1 physically interacts with the two SR proteins, FgNpl3 and FgSrp1. Overall, our results indicated that SRK1 regulates fungal development, plant infection and mRNA processing by phosphorylation of other splicing factors including SR proteins, and the spacer domain regulates the functions of Srk1 by modulating its nucleocytoplasmic shuttling.

Repetitive transcranial magnetic stimulation inhibits Sirt1/MAO-A signaling in the prefrontal cortex in a rat model of depression and cortex-derived astrocytes - Zheng-wu Peng; Fen Xue; Cui-hong Zhou; Rui-guo Zhang; Ying Wang; Ling Liu; Han-fei Sang; Hua-ning Wang; Qing-rong Tan (Molecular and Cellular Biochemistry, 2018)

Protective effect of the total flavonoids from Apocynum venetum L. on carbon tetrachloride-induced hepatotoxicity in vitro and in vivo - Wei Zhang; Zheng Dong; Xiujuan Chang; Cuihong Zhang; Guanghua Rong; Xudong Gao; Zhen Zeng; Chunping Wang; Yan Chen; Yihui Rong; Jianhui Qu; Ze Liu; et al. (Journal of Physiology and Biochemistry, 2018)

Effects of probiotic on microfloral structure of live feed used in larval breeding of turbot Scophthalmus maximus - Yan Jiang; Zheng Zhang; Yingeng Wang; Yayun Jing; Meijie Liao; Xiaojun Rong; Bin Li; Guiping Chen; Hesen Zhang (Journal of Oceanology and Limnology, 2018)

Joint Interpretation of Geological, Magnetic, AMT, and ERT Data for Mineral Exploration in the Northeast of Inner Mongolia, China - Gang Zhang; Qing-Tian Lü; Gui-Bin Zhang; Ping-Rong Lin; Zheng-Yuan Jia; Kui Suo (Pure and Applied Geophysics, 2018)

Effect of spatial variability of engineering properties on stability of a CSMC embankment - Rong-Jun Zhang; Mohammed Shareef M. S. Hasan; Jun-Jie Zheng; Yu-Shi Cheng (Marine Georesources & Geotechnology, 2018)

ALDH2 genes are negatively correlated with natural deastringency in Chinese PCNA persimmon (Diospyros kaki Thunb.) - Jun-Chi Xu; Jin-Ge Ding; Jian-Ping Gan; Rong-Li Mo; Li-Qing Xu; Qing-Lin Zhang; Zheng-Rong Luo (Tree Genetics & Genomes, 2017)

Lipid accumulation and anti-rotifer robustness of microalgal strains isolated from Eastern China - Cheng Yuan; Yan-Lin Zheng; Wan-Lu Zhang; Ru He; Yong Fan; Guang-Rong Hu; Fu-Li Li (Journal of Applied Phycology, 2017)

Fiber-type distribution and expression of myosin heavy chain isoforms in newborn heterozygous myostatin-knockout pigs - Xiao-Xu Xing; Mei-Fu Xuan; Long Jin; Qing Guo; Zhao-Bo Luo; Jun-Xia Wang; Qi-Rong Luo; Guang-Lei Zhang; Cheng-Du Cui; Zheng-Yun Cui; Jin-Dan Kang; Xi-Jun Yin (Biotechnology Letters, 2017)

Erratum to: Geometrical feature analysis and disaster assessment of the Xinmo landslide based on remote sensing data - Jian-rong Fan; Xi-yu Zhang; Feng-huan Su; Yong-gang Ge; Paolo Tarolli; Zheng-yin Yang; Chao Zeng; Zhen Zeng (Journal of Mountain Science, 2017)

Geometrical feature analysis and disaster assessment of the Xinmo landslide based on remote sensing data - Jian-rong Fan; Xi-yu Zhang; Feng-huan Su; Yong-gang Ge; Paolo Tarolli; Zheng-yin Yang; Chao Zeng; Zhen Zeng (Journal of Mountain Science, 2017)

Responses of soil nitrous oxide production and abundances and composition of associated microbial communities to nitrogen and water amendment - Qing Wang; Yu-Rong Liu; Cui-Jing Zhang; Li-Mei Zhang; Li-Li Han; Ju-Pei Shen; Ji-Zheng He (Biology and Fertility of Soils, 2017)

Assimilation of total lightning data using the three-dimensional variational method at convection-allowing resolution - Rong Zhang; Yijun Zhang; Liangtao Xu; Dong Zheng; Wen Yao (Journal of Meteorological Research, 2017)

Lower functional connectivity of default mode network in cognitively normal young adults with mutation of APP, presenilins and APOE ε4 - Yun Yan Su; Xiao Dong Zhang; U. Joseph Schoepf; Akos Varga-Szemes; Andrew Stubenrauch; Xue Liang; Li Juan Zheng; Gang Zheng; Xiang Kong; Qiang Xu; Shou Ju Wang; Rong Feng Qi; et al. (Brain Imaging and Behavior, 2017)

RepSox improves viability and regulates gene expression in rhesus monkey–pig interspecies cloned embryos - Hai-Ying Zhu; Long Jin; Qing Guo; Zhao-Bo Luo; Xiao-Chen Li; Yu-Chen Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Guang-Lei Zhang; Qi-Rong Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Microglia activation contributes to quinolinic acid-induced neuronal excitotoxicity through TNF-α - Wei Feng; Yan Wang; Zi-Qi Liu; Xuan Zhang; Rong Han; You-Zhu Miao; Zheng-Hong Qin (Apoptosis, 2017)

The genome sequence of Brassica campestris chrysovirus 1, a novel putative plant-infecting tripartite chrysovirus - Jun Zhang; Zhonghao Zhao; Rong Hu; Lingfang Guo; Limin Zheng; Zhenguo Du; Zujian Wu; Shouguo Fang; Songbai Zhang; Yong Liu (Archives of Virology, 2017)

Quinone/hydroquinone meroterpenoids with antitubercular and cytotoxic activities produced by the sponge-derived fungus Gliomastix sp. ZSDS1-F7 - Wei-Jun He; Xiao-Jiang Zhou; Xiao-Chu Qin; Yong-Xin Mai; Xiu-Ping Lin; Sheng-Rong Liao; Bin Yang; Tianyu Zhang; Zheng-Chao Tu; Jun-Feng Wang; Yonghong Liu (Natural Product Research, 2017)

Evaluating the contribution of Yr genes to stripe rust resistance breeding through marker-assisted detection in wheat - Shigang Zheng; Yunfang Li; Lu Lu; Zehou Liu; Chihong Zhang; Donghui Ao; Lirong Li; Chunyan Zhang; Rong Liu; Congpei Luo; Yu Wu; Lei Zhang (Euphytica, 2017)

The developmental competence of oocytes parthenogenetically activated by an electric pulse and anisomycin treatment - Yu-Chen Zhang; Long Jin; Hai-Ying Zhu; Qing Guo; Xiao-Chen Li; Guang-Lei Zhang; Xiao-Xu Xing; Mei-Fu Xuan; Qi-Rong Luo; Zhao-Bo Luo; Jun-Xia Wang; Cheng-Du Cui; et al. (Biotechnology Letters, 2017)

Hepatic expression of transcription factors affecting developmental regulation of UGT1A1 in the Han Chinese population - Ya-li Nie; Hang He; Jiang-feng Li; Xiang-guang Meng; Liang Yan; Pei Wang; Shu-jie Wang; Hong-zheng Bi; Li-rong Zhang; Quan-cheng Kan (European Journal of Clinical Pharmacology, 2017)

Using PG-Liposome-Based System to Enhance Puerarin Liver-Targeted Therapy for Alcohol-Induced Liver Disease - Ying-Zheng Zhao; Lu Zhang; Pardeep K. Gupta; Fu-Rong Tian; Kai-Li Mao; Kai-Yan Qiu; Wei Yang; Chuan-Zhu Lv; Cui-Tao Lu (AAPS PharmSciTech, 2016)

The angiotensin-I converting enzyme gene I/D variation contributes to end-stage renal disease risk in Chinese patients with type 2 diabetes receiving hemodialysis - Ming Lu; Jianzhong Zhang; Ming Li; Xiaoxu Ge; Xu Dai; Jiao Zhao; Mingzhou Fu; Tao Wang; Xiyao Fang; Can Li; Rong Zhang; Weijing Zhao; et al. (Molecular and Cellular Biochemistry, 2016)

Spatial and Vertical Distribution of Dechlorane Plus in Mangrove Sediments of the Pearl River Estuary, South China - Yu-Xin Sun; Zai-Wang Zhang; Xiang-Rong Xu; Qin-Wei Hao; Yong-Xia Hu; Xiao-Bo Zheng; Xiao-Jun Luo; Zeng-Hui Diao; Bi-Xian Mai (Archives of Environmental Contamination and Toxicology, 2016)

Microsatellite records for volume 8, issue 3 - Yan-Ling Cao; Lívia Izabela Caputo; Hongyi Cheng; Fausto Moreira da Silva Carmo; Leiliane Campos de Carvalho; Gabriel de Menezes Yazbeck; Zélia de Oliveira Teixeira; Jiaxin Fu; José Antonio Guerrero; Guibing Hu; Jun Li; Zhihua Lin; et al. (Conservation Genetics Resources, 2016)

Microwave-assisted Synthesis and antifungal activity of coumarin[8,7-e][1,3]oxazine derivatives - Ming-Zhi Zhang; Rong-Rong Zhang; Wen-Zheng Yin; Xiang Yu; Ya-Ling Zhang; Pin Liu; Yu-Cheng Gu; Wei-Hua Zhang (Molecular Diversity, 2016)

Erratum to: Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Injection of Aβ1-40 into hippocampus induced cognitive lesion associated with neuronal apoptosis and multiple gene expressions in the tree shrew - Na Lin; Liu-Lin Xiong; Rong-ping Zhang; Hong Zheng; Lei Wang; Zhong-Yi Qian; Piao Zhang; Zhi-wei Chen; Fa-Bao Gao; Ting-Hua Wang (Apoptosis, 2016)

Assessment of interannual sea surface salinity variability and its effects on the barrier layer in the equatorial Pacific using BNU-ESM - Hai Zhi; Rong-Hua Zhang; Fei Zheng; Pengfei Lin; Lanning Wang; Peng Yu (Advances in Atmospheric Sciences, 2016)

Role of immune tolerance in BALB/c mice with anaphylactic shock after Echinococcus granulosus infection - Qin Zhang; Jian-Rong Ye; Hai-Mei Ma; Jian-Jiang Wu; Tao Jiang; Hong Zheng (Immunologic Research, 2016)

MiR-219 Protects Against Seizure in the Kainic Acid Model of Epilepsy - Honghua Zheng; Rong Tang; Yi Yao; Zhilin Ji; Yuanyuan Cao; Zhaoji Liu; Feng Peng; Wenjie Wang; Dan Can; Huiqin Xing; Guojun Bu; Huaxi Xu; et al. (Molecular Neurobiology, 2016)

Effects of different microbes on fermenting feed for sea cucumber (Apostichopus japonicus) - Yan Jiang; Yingeng Wang; Kangsen Mai; Zheng Zhang; Meijie Liao; Xiaojun Rong (Journal of Ocean University of China, 2015)

Anti-angiogenic Effects of Bumetanide Revealed by DCE-MRI with a Biodegradable Macromolecular Contrast Agent in a Colon Cancer Model - Anthony S. Malamas; Erlei Jin; Qi Zhang; John Haaga; Zheng-Rong Lu (Pharmaceutical Research, 2015)

Modified method for estimating organic carbon density in discontinuous Karst soil using ground-penetrating radar and geostatistics - Lei Li; Yin-hang Xia; Shu-juan Liu; Wei Zhang; Xiang-bi Chen; Hua Zheng; Hu-sen Qiu; Xun-yang He; Yi-rong Su (Journal of Mountain Science, 2015)

Genome-wide characterization and analysis of F-box protein-encoding genes in the Malus domestica genome - Hao-Ran Cui; Zheng-Rong Zhang; Wei lv; Jia-Ning Xu; Xiao-Yun Wang (Molecular Genetics and Genomics, 2015)

Schwann cells induce Proliferation and Migration of Oligodendrocyte Precursor Cells Through Secretion of PDGF-AA and FGF-2 - Yue-Juan Chen; Jing-Xing Zhang; Lin Shen; Qi Qi; Xiao-Xin Cheng; Zheng-Rong Zhong; Zhi-Quan Jiang; Rui Wang; He-Zuo Lü; Jian-Guo Hu (Journal of Molecular Neuroscience, 2015)

Household pesticide exposure and the risk of childhood acute leukemia in Shanghai, China - Yan Zhang; Yu Gao; Rong Shi; Didi Chen; Xiaojin Wang; Michihiro Kamijima; Kiyoshi Sakai; Tamie Nakajima; Md. Khalequzzaman; Yijun Zhou; Ying Zheng; Pingping Bao; et al. (Environmental Science and Pollution Research, 2015)

Construction of cDNA library from Prunus campanulata leaves and preliminary expressed sequence tag (EST) analysis during cold stress - Ying-Hui Zhang; Jun-Dong Rong; Li-Guang Chen; Ling-Yan Chen; Tian-You He; Yu-Shan Zheng (Biologia, 2015)

High immune activation and abnormal expression of cytokines contribute to death of SHIV89.6-infected Chinese rhesus macaques - Ren-Rong Tian; Ming-Xu Zhang; Lin-Tao Zhang; Xiao-Liang Zhang; Hong-Yi Zheng; Lin Zhu; Wei Pang; Gao-Hong Zhang; Yong-Tang Zheng (Archives of Virology, 2015)

The E23K and A190A variations of the KCNJ11 gene are associated with early-onset type 2 diabetes and blood pressure in the Chinese population - Langen Zhuang; Yu Zhao; Weijing Zhao; Ming Li; Ming Yu; Ming Lu; Rong Zhang; Xiaoxu Ge; Taishan Zheng; Can Li; Jun Yin; Jingyuan Yin; et al. (Molecular and Cellular Biochemistry, 2015)

Interannually varying salinity effects on ENSO in the tropical pacific: a diagnostic analysis from Argo - Fei Zheng; Rong-Hua Zhang (Ocean Dynamics, 2015)

Relationships between heavy metal concentrations in soils and reclamation history in the reclaimed coastal area of Chongming Dongtan of the Yangtze River Estuary, China - Chao Ma; Rong Zheng; Jiale Zhao; Xiumei Han; Li Wang; Xiaojiang Gao; Chaosheng Zhang (Journal of Soils and Sediments, 2015)

Halovenus rubra sp. nov., Isolated from Salted Brown Alga Laminaria - Dong Han; Wen-Jiao Zhang; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2015)

Retraction Note to: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2014)

Hepatocellular Carcinoma in Budd-Chiari Syndrome: Enhancement Patterns at Dynamic Gadolinium-Enhanced T1-Weighted MR Imaging - Chun Yang; Kai Xu; Junnian Zheng; Ping Ma; Chunfeng Hu; Shaodong Li; Yutao Rong; Xin Lu; Qingqiao Zhang; Maoheng Zu; Rong Hua; Ling Zhang (Cell Biochemistry and Biophysics, 2014)

Response of bacterial pdo1, nah, and C12O genes to aged soil PAH pollution in a coke factory area - Xue-Mei Han; Yu-Rong Liu; Yuan-Ming Zheng; Xiao-Xia Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Analysis of aroma-active compounds in three sweet osmanthus (Osmanthus fragrans) cultivars by GC-olfactometry and GC-MS - Xuan Cai; Rong-zhang Mai; Jing-jing Zou; Hong-yan Zhang; Xiang-ling Zeng; Ri-ru Zheng; Cai-yun Wang (Journal of Zhejiang University-SCIENCE B, 2014)

Structural modification of an EGFR inhibitor that showed weak off-target activity against RET leading to the discovery of a potent RET inhibitor - Qi-Zheng Sun; Yong Xu; Jing-Jing Liu; Chun-Hui Zhang; Ze-Rong Wang; Ren-Lin Zheng; Wen-Jing Wang; Lin-Li Li; Sheng-Yong Yang (Molecular Diversity, 2014)

Effects of land cover on soil organic carbon stock in a karst landscape with discontinuous soil distribution - Xiang-bi Chen; Hua Zheng; Wei Zhang; Xun-yang He; Lei Li; Jin-shui Wu; Dao-you Huang; Yi-rong Su (Journal of Mountain Science, 2014)

Effects of interannual salinity variability on the barrier layer in the western-central equatorial Pacific: A diagnostic analysis from Argo - Fei Zheng; Rong-Hua Zhang; Jiang Zhu (Advances in Atmospheric Sciences, 2014)

Analyzing and modeling rheological behavior of liver fibrosis in rats using shear viscoelastic moduli - Ying Zhu; Yi Zheng; Yuan-yuan Shen; Xin Chen; Xin-yu Zhang; Hao-ming Lin; Yan-rong Guo; Tian-fu Wang; Si-ping Chen (Journal of Zhejiang University-SCIENCE B, 2014)

Characterization of eubacterial and archaeal community diversity in the pit mud of Chinese Luzhou-flavor liquor by nested PCR–DGGE - Xiao-Fei Ding; Chong-De Wu; Li-Qiang Zhang; Jia Zheng; Rong-Qing Zhou (World Journal of Microbiology and Biotechnology, 2014)

The Leu72Met polymorphism of the GHRL gene prevents the development of diabetic nephropathy in Chinese patients with type 2 diabetes mellitus - Langen Zhuang; Ming Li; Changhua Yu; Can Li; Mingming Zhao; Ming Lu; Taishan Zheng; Rong Zhang; Weijing Zhao; Yuqian Bao; Kunsan Xiang; Weiping Jia; et al. (Molecular and Cellular Biochemistry, 2014)

Halobellus litoreus sp. nov., a Halophilic Archaeon Isolated from a Chinese Marine Solar Saltern - Mei-Lin Zhao; Xing-Xing Qiu; Wen-Jiao Zhang; Dong Han; Heng-Lin Cui; Zheng-Rong Li (Current Microbiology, 2014)

Linkage between community diversity of sulfate-reducing microorganisms and methylmercury concentration in paddy soil - Yu-Rong Liu; Yuan-Ming Zheng; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2014)

Isolation and characterization of fifteen polymorphic tetranucleotide microsatellite loci in Schizopygopsis younghusbandi Regan - Huan Zheng; Gui-Rong Zhang; Shan-Shan Guo; Kai-Jian Wei; Cong-Xin Xie; Tai-Ming Ge (Conservation Genetics Resources, 2013)

Transjugular intrahepatic portosystemic shunt induced short- and long-term cerebral blood flow variations in cirrhotic patients: an arterial spin labeling MRI study - Gang Zheng; Long Jiang Zhang; Yue Cao; Zhiying Pan; Rong Feng Qi; Ling Ni; Donghong Shi; Xinxin Fan; Guang Ming Lu (Metabolic Brain Disease, 2013)

Halobellus rarus sp. nov., a halophilic archaeon from an inland salt lake of China - Wen-Jiao Zhang; Dong Han; Xing-Xing Qiu; Mei-Lin Zhao; Yun-Zhuang Mou; Heng-Lin Cui; Zheng-Rong Li (Antonie van Leeuwenhoek, 2013)

Physical characteristics of Chinese Hakka - LianBin Zheng; YongLan Li; ShunHua Lu; JinPing Bao; Yang Wang; XiaoRui Zhang; Hong Xue; WenGuo Rong (Science China Life Sciences, 2013)

Response of leaf, sheath and stem nutrient resorption to 7 years of N addition in freshwater wetland of Northeast China - Rong Mao; Chang-Chun Song; Xin-Hou Zhang; Xian-Wei Wang; Zheng-Hai Zhang (Plant and Soil, 2013)

RETRACTED ARTICLE: Characterization of cancer stem-like cells in the side population cells of human gastric cancer cell line MKN-45 - Hai-hong Zhang; Ai-zhen Cai; Xue-ming Wei; Li Ding; Feng-zhi Li; Ai-ming Zheng; Da-jiang Dai; Rong-rong Huang; Hou-jun Cao; Hai-yang Zhou; Jian-mei Wang; Xue-jing Wang; et al. (Journal of Zhejiang University-SCIENCE B, 2013)

Paroxetine up-regulates neurogenesis in hippocampus-derived neural stem cell from fetal rats - Zheng-wu Peng; Fen Xue; Hua-ning Wang; Rui-guo Zhang; Yun-chun Chen; Ying Wang; Li-yi Zhang; Juan Fan; Qing-rong Tan (Molecular and Cellular Biochemistry, 2013)

Methods to measure and analyze ciliary beat activity: Ca2+ influx-mediated cilia mechanosensitivity - Wen-Er Li; Weiwei Chen; Yun-Fei Ma; Qing-Rong Tuo; Xiao-Jing Luo; Ting Zhang; Wen-Bo Sai; Jing Liu; Jinhua Shen; Zhi-Gang Liu; Yun-Min Zheng; Yong-Xiao Wang; et al. (Pflügers Archiv - European Journal of Physiology, 2012)

Antioxidant system of tea (Camellia sinensis) leaves in response to phosphorus supply - Zheng-He Lin; Li-Song Chen; Rong-Bing Chen; Fang-Zhou Zhang (Acta Physiologiae Plantarum, 2012)

A fully automatic registration approach based on contour and SIFT for HJ-1 images - XiLiang Ni; ChunXiang Cao; Lin Ding; Tao Jiang; Hao Zhang; HuiCong Jia; GuangHe Li; Jian Zhao; Wei Chen; Wei Ji; Min Xu; MengXu Gao; et al. (Science China Earth Sciences, 2012)

Synthesis of aspirin eugenol ester and its biological activity - Jian-yong Li; Yuan-guang Yu; Qi-wen Wang; Ji-yu Zhang; Ya-jun Yang; Bing Li; Xu-zheng Zhou; Jian-rong Niu; Xiao-juan Wei; Xi-wang Liu; Zhi-qi Liu (Medicinal Chemistry Research, 2012)

Modulation of El Niño-Southern Oscillation by freshwater flux and salinity variability in the tropical Pacific - Rong-Hua Zhang; Fei Zheng; Jieshun Zhu; Yuhua Pei; Quanan Zheng; Zhanggui Wang (Advances in Atmospheric Sciences, 2012)

Imprinting analysis of porcine DIO3 gene in two fetal stages and association analysis with carcass and meat quality traits - Mu Qiao; Hua-Yu Wu; Ling Guo; Shu-Qi Mei; Peng-Peng Zhang; Feng-E Li; Rong Zheng; Chang-Yan Deng (Molecular Biology Reports, 2012)

Functional analysis of the HS185 regulatory element in the rice HSP70 promoter - Yu-Man Zhang; Yu-Mei Zheng; Na Xiao; Li-Na Wang; Yao Zhang; Rong-Xiang Fang; Xiao-Ying Chen (Molecular Biology Reports, 2012)

Molecular characterization, expression pattern, and association analysis with carcass traits of the porcine SHIP2 gene - Qi Xiong; Jin Chai; Changyan Deng; Siwen Jiang; Xiaofeng Li; Xiaojun Suo; Nian Zhang; Qianping Yang; Yang Liu; Rong Zheng; Mingxin Chen (Molecular and Cellular Biochemistry, 2012)

Single nucleotide polymorphism of CACNA2D1 gene and its association with milk somatic cell score in cattle - Zheng Rong Yuan; Jiao Li; Li Liu; Lu Pei Zhang; Li Min Zhang; Cui Chen; Xiao Jie Chen; Xue Gao; Jun Ya Li; Jin Bao Chen; Hui Jiang Gao; Shang Zhong Xu (Molecular Biology Reports, 2011)

Enhanced Biotransformation of 2-Phenylethanol with Ethanol Oxidation in a Solid–Liquid Two-Phase System by Active Dry Yeast - Shaofeng Rong; Baomei Ding; Xiaoli Zhang; Xuesong Zheng; Yifei Wang (Current Microbiology, 2011)

Association of thyroglobulin gene variants with carcass and meat quality traits in beef cattle - Guan-Yu Hou; Zheng-Rong Yuan; Han-Lin Zhou; Lu-Pei Zhang; Jun-Ya Li; Xue Gao; Dong-Jing Wang; Hui-Jiang Gao; Shang-Zhong Xu (Molecular Biology Reports, 2011)

Genome-wide analysis of OCT4 binding sites in glioblastoma cancer cells - Xue-feng Fang; Wei-yi Zhang; Na Zhao; Wei Yu; Dong Ding; Xu Hong; Li-sha Li; Hua-rong Zhang; Shu Zheng; Biao-yang Lin (Journal of Zhejiang University-SCIENCE B, 2011)

Effect of dietary fatty acids on serum parameters, fatty acid compositions, and liver histology in Shaoxing laying ducks - Wei-meng Liu; Shu-jing Lai; Li-zhi Lu; Fang-xiong Shi; Jing Zhang; Yu Liu; Bo Yu; Zheng-rong Tao; Jun-da Shen; Guo-qin Li; De-qian Wang; Jin-jun Li; et al. (Journal of Zhejiang University-SCIENCE B, 2011)

M. tuberculosis H37Rv Infection of Chinese Rhesus Macaques - Jing Zhang; Yan-Qing Ye; Yong Wang; Ping-Zheng Mo; Qiao-Yang Xian; Yan Rao; Rong Bao; Ming Dai; Jun-Yan Liu; Ming Guo; Xin Wang; Zhi-Xiang Huang; et al. (Journal of Neuroimmune Pharmacology, 2011)

Satellite altimeter observations of nonlinear Rossby eddy–Kuroshio interaction at the Luzon Strait - Quanan Zheng; Chang-Kuo Tai; Jianyu Hu; Hongyang Lin; Rong-Hua Zhang; Feng-Chun Su; Xiaofeng Yang (Journal of Oceanography, 2011)

Overexpression of PGC-1β improves insulin sensitivity and mitochondrial function in 3T3-L1 adipocytes - Chun-Lin Gao; Guang-Ling Liu; Shi Liu; Xiao-Hui Chen; Chen-Bo Ji; Chun-Mei Zhang; Zheng-Kun Xia; Xi-rong Guo (Molecular and Cellular Biochemistry, 2011)

Increased urinary 8-hydroxy-2′-deoxyguanosine levels in workers exposed to di-(2-ethylhexyl) phthalate in a waste plastic recycling site in China - Qian Wang; Li Wang; Xi Chen; Kai Min Rao; Shao You Lu; Sheng Tao Ma; Pu Jiang; Dan Zheng; Shun Qing Xu; Hong Yan Zheng; Jian Shu Wang; Zhi Qiang Yu; et al. (Environmental Science and Pollution Research, 2011)

Endophytic fungus Cladosporium cladosporioides LF70 from Huperzia serrata produces Huperzine A - Zhi Bin Zhang; Qing Gui Zeng; Ri Ming Yan; Ya Wang; Zheng Rong Zou; Du Zhu (World Journal of Microbiology and Biotechnology, 2011)

Quantitative estimation of the shrub canopy LAI from atmosphere-corrected HJ-1 CCD data in Mu Us Sandland - Wei Chen; ChunXiang Cao; QiSheng He; HuaDong Guo; Hao Zhang; RenQiang Li; Sheng Zheng; Min Xu; MengXu Gao; Jian Zhao; Sha Li; XiLiang Ni; et al. (Science China Earth Sciences, 2010)

Laser altimetry data of Chang’E-1 and the global lunar DEM model - ChunLai Li; Xin Ren; JianJun Liu; XiaoDuan Zou; LingLi Mu; JianYu Wang; Rong Shu; YongLiao Zou; HongBo Zhang; Chang Lü; JianZhong Liu; Wei Zuo; et al. (Science China Earth Sciences, 2010)

The complete mitogenome and phylogenetic analysis of Bombyx mandarina strain Qingzhou - Xiao-long Hu; Guang-li Cao; Ren-yu Xue; Xiao-jian Zheng; Xing Zhang; Hai-rong Duan; Cheng-liang Gong (Molecular Biology Reports, 2010)

Effects of mercury on the activity and community composition of soil ammonia oxidizers - Yu-Rong Liu; Yuan-Ming Zheng; Ju-Pei Shen; Li-Mei Zhang; Ji-Zheng He (Environmental Science and Pollution Research, 2010)

New cyclopentenones from strain Trichoderma sp. YLF-3 - Guo-Hong Li; Li-Jun Zheng; Fang-Fang Liu; Li-Zhi Dang; Lei Li; Rong Huang; Ke-Qin Zhang (Natural Product Research, 2009)

Combination of newly developed high quality Fuqu with traditional Daqu for Luzhou-flavor liquor brewing - Wen-Xue Zhang; Zheng-Yun Wu; Qi-Sheng Zhang; Rong Wang; Heng Li (World Journal of Microbiology and Biotechnology, 2009)

Comparison of four molecular markers for genetic analysis in Diospyros L. (Ebenaceae) - X. Y. Du; Q. L. Zhang; Zheng-Rong Luo (Plant Systematics and Evolution, 2009)

Molecular cytogenetic characterization of wheat–Secale africanum amphiploids and derived introgression lines with stripe rust resistance - Zu-Jun Yang; Guang-Rong Li; Ju-Qing Jia; Xue Zeng; Meng-Ping Lei; Zi-Xian Zeng; Tao Zhang; Zheng-Long Ren (Euphytica, 2009)

Molecular cloning and expression profiling of the first specific jasmonate biosynthetic pathway gene allene oxide synthase from Lonicera japonica - Keji Jiang; Yan Pi; Rong Hou; Hainian Zeng; Zhuoshi Huang; Zheng Zhang; Xiaofen Sun; Kexuan Tang (Molecular Biology Reports, 2009)

Ensemble hindcasts of ENSO events over the past 120 years using a large number of ensembles - Fei Zheng; Jiang Zhu; Hui Wang; Rong-Hua Zhang (Advances in Atmospheric Sciences, 2009)

Identification of α-gliadin genes in Dasypyrum in relation to evolution and breeding - Guang-Rong Li; Cheng Liu; Zi-Xian Zeng; Ju-Qing Jia; Tao Zhang; Jian-Ping Zhou; Zheng-Long Ren; Zu-Jun Yang (Euphytica, 2009)

Systematic biotic responses to palaeoenvironmental change in the Late Pleistocene southern South China Sea: a preliminary study - Muhong Chen; Qianyu Li; Lanlan Zhang; Fan Zheng; Jun Lu; Rong Xiang; Lili Zhang; Wen Yan; Zhong Chen; Shangbin Xiao (Journal of Quaternary Science, 2008)
Oxygen and carbon isotopes from the planktonic foraminifer Globigerinoides sacculifer , trace element contents, calcium carbonate, biogenic silica, grain size, and abundances of diatoms, radiolarians and foraminifera in a deep‐sea core from the southwestern South China Sea were analysed to investigate the response of various marine ecological communities to environmental changes over the last 200 ka. The synthesised results show that the quality of the palaeoecological environment for biological growth is primarily affected by nutrient supply and terrigenous disturbance. Ba and P are important nutrient elements for the growth of diatoms, radiolarians and planktonic foraminifera. Together with dissolved silica and calcium carbonate in sea water, these elements may control microbiotic development. However, variations in Fe content appear to affect diatom and radiolarian abundance. Optimal biotic growth occurs when nutrients are abundant and when there is minimal terrigenous disturbance. Biotic growth decreases when sea water is highly oligotrophic and terrigenous input is high. Maximum biological growth occurred in the mid Holocene, but deteriorated soon afterwards owing to increased terrigenous input, causing a decrease of biological abundance and productivity in the late Holocene. The results also indicate how the Toba volcanic eruption ca. 74 ka ago contributed to changing the ecological environment in the southern South China Sea. Copyright © 2008 John Wiley & Sons, Ltd.

Microbial composition and diversity of an upland red soil under long-term fertilization treatments as revealed by culture-dependent and culture-independent approaches - Ji-Zheng He; Yong Zheng; Cheng-Rong Chen; Yuan-Qiu He; Li-Mei Zhang (Journal of Soils and Sediments, 2008)

Cadmium Accumulation in the Edible Parts of Different Cultivars of Radish, Raphanus sativus L., and Carrot, Daucus carota var. sativa, Grown in a Cd-contaminated Soil - Rui-Lun Zheng; Hua-Fen Li; Rong-Feng Jiang; Fu-Suo Zhang (Bulletin of Environmental Contamination and Toxicology, 2008)

Nematicidal coumarins from Heracleum candicans Wall. - Xing-Biao Wang¶; Guo-Hong Li¶; Lei Li; Li-Jun Zheng; Rong Huang; Ke-Qin Zhang (Natural Product Research, 2008)

Proteiomic patterns for endometrial cancer using SELDI-TOF-MS - Li-rong Zhu; Wen-ying Zhang; Li Yu; Yan-hua Zheng; Jun Hu; Qin-ping LIAO (Journal of Zhejiang University-SCIENCE B, 2008)

Validating a segment on the short arm of chromosome 6 responsible for genetic variation in the hull silicon content and yield traits of rice - Wei-Min Dai; Ke-Qin Zhang; Ji-Rong Wu; Lei Wang; Bin-Wu Duan; Kang-Le Zheng; Run Cai; Jie-Yun Zhuang (Euphytica, 2008)

Isolation of a new repetitive DNA sequence from Secale africanum enables targeting of Secale chromatin in wheat background - Cheng Liu; Zu-Jun Yang; Guang-Rong Li; Zi-Xian Zeng; Yong Zhang; Jian-Ping Zhou; Zhao-Hui Liu; Zheng-Long Ren (Euphytica, 2008)

Quantitative trait loci for carcass traits on pig chromosomes 4, 6, 7, 8 and 13 - Jing Hu Zhang; Yuan Zhu Xiong; Bo Zuo; Ming Gang Lei; Si Wen Jiang; Feng E Li; Rong Zheng; Jia Lian Li; Quan De Xu (Journal of Applied Genetics, 2007)

Dependent mechanism of Chinese prepositions processing in the brain: evidence from event-related potentials - Huan-Hai Fang; Rong-Ping Zhang; Huan-Fei Fang; Ming-Yang Gao; Min Zheng; Xiao-Yu Sun (Neuroscience Bulletin, 2007)

Lance-adams syndrome: a report of two cases - Yan-xing Zhang; Jian-ren Liu; Biao Jiang; Hui-qin Liu; Mei-ping Ding; Shui-jiang Song; Bao-rong Zhang; Hong Zhang; Bin Xu; Huai-hong Chen; Zhong-jin Wang; Jian-zheng Huang (Journal of Zhejiang University-SCIENCE B, 2007)

Family history of hematopoietic and non-hematopoietic malignancies and risk of non-Hodgkin lymphoma - Yawei Zhang; Rong Wang; Theodore R. Holford; Brian Leaderer; Shelia Hoar Zahm; Peter Boyle; Yong Zhu; Qin Qin; Tongzhang Zheng (Cancer Causes & Control, 2007)

Improved ENSO forecasts by assimilating sea surface temperature observations into an intermediate coupled model - Fei Zheng; Jiang Zhu; Rong-Hua Zhang; Guangqing Zhou (Advances in Atmospheric Sciences, 2006)

Polymorphism of the mouse gene for the interleukin 10 receptor alpha chain (Il10ra) and its association with the autoimmune phenotype - Zan-Mei Qi; Jun Wang; Zheng-Rong Sun; Feng-Mao Ma; Qing-Rui Zhang; Sachiko Hirose; Yi Jiang (Immunogenetics, 2005)

Co-inheritance of specific genotypes of HSPG and ApoE gene increases risk of type 2 diabetic nephropathy - Limei Liu; Kunsan Xiang; Taishan Zheng; Rong Zhang; Ming Li; Jie Li (Molecular and Cellular Biochemistry, 2003)

The heparan sulfate proteoglycan gene polymorphism: Association with type 2 diabetic nephropathy in Chinese - Limei Liu; Kunsan Xiang; Taishan Zheng; Rong Zhang; Ming Li; Yanqing Wang; Huijuan Li; Jie Li (Molecular and Cellular Biochemistry, 2003)